Composite fiber, multifilament, braided fabric, and fiber product
By using composite fibers in textiles, multiple segments B with small sections of sections B are arranged on the cross section of the fiber to form islands or core sheath composite fibers, the problem of difficult to maintain high durability, good touch and high water removal performance for clothing textiles under long-term wear and friction wear, and the balance of these properties is achieved.
Patent Information
- Application Number
- CN202380066598.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-29
- Filing Date
- 2023-09-14
- Publication Date
- 2025-04-25
AI Technical Summary
The prior art is difficult to achieve both high durability, good touch and high water repellency in textiles for clothing, especially in the case of long wear and friction wear.
A composite fiber is used, and there are two types of segment A and segment B on the fiber cross-section. Section B has a smaller section area and is formed of a composite polymer that is parallel or eccentric core sheath type. Multiple segments B are arranged on the fiber cross-section to form island composite fibers or core sheath composite fibers.
The textile has a dry touch or a soft feel that has a rebound feeling, while suppressing the surface quality reduction caused by friction and wear, and showing high water removal performance.
Smart Images

Figure CN119895088A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a composite fiber, a multifilament, a braided fabric and a fiber product. Background Art
[0002] Synthetic fibers including polyester, polyamide, and the like have excellent mechanical properties and dimensional stability, and therefore are widely used in a wide range of applications, from clothing to non-clothing applications.
[0003] Work clothes or school uniforms are mostly worn every day, but factory workers or students who wear such clothes are very active, which easily causes pilling or wear, and fabrics with higher durability are used. Therefore, in order to improve the durability of fabrics used for such clothes, fibers with high rigidity and coarse denier are mostly used, and warp and weft yarns are densely crossed and strongly constrained to each other. Therefore, compared with textiles used in general clothing, the touch or softness is sometimes poor, which sometimes hinders the wearing feeling or comfort when wearing.
[0004] In addition, the fibers of the above-mentioned fabrics such as clothes are constrained due to the low elasticity of the warp and weft. Due to friction with the floor, ironing, long-term wearing, friction with other raw materials, wear, etc., sometimes the so-called polishing phenomenon occurs in the worn parts with time, where the gloss increases, and the surface quality of the textiles is reduced. This polishing phenomenon occurs because the uneven structure of the textile surface is flattened due to the deformation or wear of the fibers, and the reflection of light increases. As a method of suppressing the phenomenon, a method of adding a smoothing agent such as silicone or polyethylene wax in post-processing has been proposed.
[0005] The purpose of adding a smoothing agent in the post-processing is to reduce the friction of the fiber surface by using the smoothing agent, thereby suppressing the deformation or wear of the fiber and preventing the occurrence of a polishing phenomenon caused by the flattening of the textile surface. However, in the method, sometimes the adhesion of the smoothing agent causes the hand feel to become hard, or the smoothing agent falls off during washing, etc., resulting in poor durability.
[0006] Therefore, various fiber technologies have been proposed, that is, fiber technologies that suppress the polishing phenomenon in textiles without impairing the feel or durability by working on the cross section or morphology of the fiber instead of post-processing.
[0007] Patent Document 1 proposes a composite fiber in which a low-melting-point polymer having a lower melting point than polyester is arranged inside a polyester fiber. In the composite fiber, the friction heat generated by friction with a floor or the like is absorbed by the heat absorption caused by the melting of the low-melting-point polymer in the core before the polyester melts, thereby suppressing fiber deformation caused by the melting of the polyester and suppressing the polishing phenomenon in the textile.
[0008] Furthermore, Patent Document 2 proposes a false twisted yarn obtained by air interlacing yarns, wherein the air interlaced yarns are configured with multifilaments containing self-extensible polyester fibers as sheath yarns and multifilaments containing polyester fibers having a higher boiling water shrinkage rate than the sheath yarns as core yarns. In a textile using the processed yarn, air interlacing is used to wrap the sheath yarns around the core yarns to form gaps between the core yarns and the sheath yarns, thereby showing a soft feel, and further, a slight curl is given by false twisting, thereby reducing the flattening of the gaps between the core yarns and the sheath yarns caused by pressing, and suppressing the polishing phenomenon during ironing.
[0009] Prior art literature
[0010] Patent Literature
[0011] Patent Document 1: Japanese Patent Application Publication No. 2017-186680 (claims)
[0012] Patent Document 2: Japanese Patent Application Publication No. 2000-314038 (claims) Summary of the invention
[0013] Problems to be solved by the invention
[0014] As disclosed in Patent Document 1, if a low melting point polymer can be arranged to absorb frictional heat, it is possible to suppress fiber deformation caused by melting of the polymer.
[0015] However, Patent Document 1 is based on the technical concept of suppressing the polishing phenomenon caused by frictional heat generated instantaneously due to friction with the floor, etc. When a textile containing the composite fiber of Patent Document 1 is worn for a long time, the surface of the textile gradually becomes flat due to abrasion with other raw materials or flattening due to pressure, and polishing phenomenon may occur. Furthermore, from the viewpoint of interfacial peeling between polyester and low-melting-point polymer, the fiber diameter or fiber morphology is limited in order to ensure abrasion resistance, so the touch and softness may be poor.
[0016] In addition, as shown in Patent Document 2, by using air to interweave around the core wire and the sheath wire to form a gap between the core wire and the sheath wire, and then using a false twisting process to give a slight curl, it is possible to reduce the flattening of the gap between the core wire and the sheath wire caused by pressing, and to suppress the polishing phenomenon caused by momentary pressing during ironing, etc.
[0017] However, when a textile product including the processed yarn of Patent Document 2 is worn for a long time, friction is applied to the sheath yarn while it is flattened by pressure, so that both the core yarn and the sheath yarn are worn, and the surface of the processed yarn gradually becomes flat, which sometimes causes a polishing phenomenon, and then the sheath yarn is pulled out due to friction, causing fuzzing, etc., and there are also cases where the durability is poor.
[0018] As described above, although there is fiber technology that can suppress the polishing phenomenon caused by momentary frictional heat or pressure, there is no fiber technology that can suppress the polishing phenomenon caused by wear with other raw materials during long-term wear, not to mention that it is difficult to achieve the important touch or feel of clothing textiles, and thus functionality at the same time.
[0019] Therefore, the present invention solves the problems of the prior art and aims to provide a composite fiber, multifilament, woven fabric or fiber product suitable for clothing textiles, wherein the composite fiber, multifilament, woven fabric or fiber product suitable for clothing textiles has a dry touch or a soft feel with a resilient feel, and can also suppress the degradation of surface quality caused by friction and wear with other raw materials, and further exhibits high water-repellent performance when a water-repellent treatment is performed.
[0020] Technical means of solving problems
[0021] The problem of the present invention is solved by the following means.
[0022] (1) A composite fiber, comprising two types of segments, segment A and segment B, in a cross section of the fiber, wherein segment B has a smaller cross-sectional area than segment A and is formed of two polymers composited in a side-by-side type or an eccentric core-sheath type,
[0023] (2) The composite fiber according to (1) above, wherein three or more segments B are arranged on the periphery of the segment A in the cross section of the fiber,
[0024] (3) The composite fiber according to (1) or (2), wherein the cross-sectional area S of each segment B in the cross-sectional surface of the fiber is B 1μm 2 ≦S B <65μm 2 ,
[0025] (4) The composite fiber according to any one of (1) to (3) is a sea-island composite fiber in which segments A and B are island components, and the sea component is formed by a polymer having the fastest dissolution rate in the solvent among the polymers constituting the sea-island composite fiber;
[0026] (5) A multifilament obtained by dividing the composite fiber according to any one of (1) to (4) into segments A and B,
[0027] (6) A fiber product, at least a part of which contains the multifilament according to (5),
[0028] (7) A multifilament comprising two types of filaments A and filaments B, wherein one or more filaments B exist between any two filaments A in the multifilament, the filaments B have a smaller fiber diameter than the filaments A and are formed of two polymers compounded in a side-by-side type or an eccentric core-sheath type,
[0029] (8) The multifilament according to (7), wherein the fiber diameter D of the filament B is B 1μm≦D B <9μm,
[0030] (9) A woven fabric, at least a portion of which contains the multifilament according to (7) or (8),
[0031] (10) The knitted fabric according to (9) is subjected to water-repellent treatment.
[0032] (11) A woven fabric comprising a multifilament comprising two types of filaments, filaments A and filaments B, wherein there is one or more filaments B between any two filaments A in the multifilament, the filaments B have a smaller fiber diameter than the filaments A and are formed of two polymers compounded into a parallel type or an eccentric core-sheath type, and the water droplet sliding angle of the woven fabric is 1 degree to 20 degrees, and the woven fabric is subjected to water repellency treatment,
[0033] (12) The knitted fabric according to (11), wherein the difference in water droplet falling angle before and after washing by Japanese Industrial Standards (JIS) L1930-2014-C4M method and drying by A method (hanging drying) is 0 to 20 degrees,
[0034] (13) The knitted fabric according to (11) or (12), wherein the fluorine content measured by combustion ion chromatography is 25 ng / g or less.
[0035] Effects of the Invention
[0036] The composite fiber, multifilament, woven fabric and fiber product of the present invention have a special fiber morphology in which the cross-sectional configuration within the composite fiber and the fiber configuration in the multifilament are precisely controlled, so that a textile having a dry touch or a soft feel with a resilient feel can be obtained, and the degradation of the surface quality caused by friction and wear with other raw materials can be suppressed. Furthermore, due to its fine and complex surface irregularities, it exhibits high water-repellent performance when a water-repellent treatment is applied. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] [ Figure 1 ] Figure 1 (a), (b), (c), and (d) are schematic diagrams showing an example of the cross-sectional structure of the conjugate fiber of the present embodiment.
[0038] [ Figure 2 ] Figure 2 (a), (b), and (c) are schematic diagrams showing an example of the cross-sectional structure of the conjugate fiber according to the present embodiment.
[0039] [ Figure 3 ] Figure 3 (a) and (b) are schematic diagrams showing an example of a cross-sectional structure of a conventional composite fiber.
[0040] [ Figure 4 ] Figure 4 This is a diagram for understanding that one or more filaments B exist between any two filaments A in the multifilament yarn of the present embodiment, and the dotted lines of the outer frame indicate the upper, lower, left, and right sides of the captured image.
[0041] [ Figure 5 ] Figure 5 (a) and (b) are schematic diagrams showing an example of the cross-sectional structure of the filament constituting the multifilament of the present embodiment. Figure 5 (a) is a schematic diagram of the cross-sectional structure of filament A. Figure 5 (b) is a schematic diagram of the cross-sectional structure of filament B.
[0042] [ Figure 6 ] Figure 6 (a), (b), and (c) are schematic diagrams showing an example of the cross-sectional structure of the filament constituting the multifilament of the present embodiment. Figure 6 (a) is a schematic diagram of the cross-sectional structure of filament A. Figure 6 (b) and Figure 6 (c) is a schematic diagram of the cross-sectional structure of filament B.
[0043] [ Figure 7 ] Figure 7 (a) and Figure 7 (b) is a schematic diagram showing an example of a cross-sectional structure of a filament constituting the multifilament of the present embodiment. Figure 7 (a) is a schematic diagram of the cross-sectional structure of filament A. Figure 7 (b) is a schematic diagram of the cross-sectional structure of filament B.
[0044] [ Figure 8 ] Figure 8 (a) and (b) are schematic diagrams showing an example of the cross-sectional structure of the filament constituting the multifilament of the present embodiment. Figure 8 (a) is a schematic diagram of the cross-sectional structure of filament A. Figure 8 (b) is a schematic diagram of the cross-sectional structure of filament B.
[0045] [ Fig. 9 ] Fig. 9 (a) and (b) are schematic diagrams showing an example of the cross-sectional structure of the filament constituting the multifilament of the present embodiment. Fig. 9 (a) is a schematic diagram of the cross-sectional structure of filament A. Fig. 9 (b) is a schematic diagram of the cross-sectional structure of filament B.
[0046] [ Fig.10 ] Fig.10 (a) and (b) are schematic diagrams showing an example of a cross-sectional structure of a filament constituting a conventional multifilament.
[0047] [ Fig.11 ] Fig.11 This is a schematic diagram showing an example of a cross-sectional structure of a filament constituting a conventional multifilament.
[0048] [ Fig.12 ] Fig.12 This is a cross-sectional view of a die for explaining the method for producing the conjugate fiber and the multifilament according to the present embodiment. DETAILED DESCRIPTION
[0049] Hereinafter, the present invention will be described in detail together with the preferred embodiments.
[0050] After a detailed analysis of the polishing phenomenon caused by abrasion with other raw materials in existing raw materials, it was found that due to the abrasion of the fibers, part of the single fiber was worn away, and the gloss did not necessarily increase in the flat part, but the gloss increased in the part where the flat parts of multiple fibers were arranged horizontally. It is estimated that the reason is that even if the flat part formed on a single fiber with a fiber diameter of about tens of μm reflects light strongly, the light reaching the human eye is small, but the fiber bundle consisting of multiple fibers is worn on the surface to form a large flat part of about hundreds of μm, which causes a part of the cloth to cause strong light reflection, and people can recognize the light.
[0051] That is, in order to suppress the polishing phenomenon that occurs over time, which is a problem of existing raw materials, it is important to form a fiber morphology that suppresses the area of the flat portion caused by friction, wear, etc. of the fiber. In order to achieve this, the inventors and others have conducted intensive research and found that by making a multifilament in which ultrafine fibers with fiber diameters reduced to a certain range are mixed with ordinary fibers, the textile has sufficient durability as a textile, and even in the case of repeated wear with other raw materials, no flat portion is formed in the fiber bundle. It is further found that due to the effect of ultrafine fibers, the softness of the textile is improved, and the rebound feeling can be maintained by mixing with ordinary fibers, making it a textile for clothing that takes into account both the tolerance to friction and the feel that the existing raw materials do not have. In addition, the ordinary fibers and ultrafine fibers mentioned here refer to a system in which single fibers with different fiber diameters are mixed, and the fibers with relatively large fiber diameters are called ordinary fibers, and the fibers with small fiber diameters are called ultrafine fibers.
[0052] In addition, in the present invention, the ultrafine fibers arranged on the surface of the fiber bundle have curling, and due to the steric hindrance caused by the curling, fine gaps are formed between the fibers, and the friction surface is not fixed but can move flexibly. Therefore, compared with the fiber bundle in which the ultrafine fibers are usually arranged on the surface, the tolerance to friction is further improved, and the polishing phenomenon that is a problem of existing raw materials can be greatly suppressed.
[0053] In addition, it was found that by mixing crimped ultrafine fibers with ordinary fibers and arranging them on the surface layer, fine and complex irregularities were formed on the surface of the textile, so that softness and a dry touch that are important in clothing textiles can be obtained. In addition, when a water-repellent treatment is applied, high water-repellent performance is exhibited, thereby completing the present invention.
[0054] Specifically, the present invention requires that there are two types of segments A and B in the fiber cross section of the composite fiber, and segment B has a smaller cross-sectional area than segment A and is composed of two polymers composited in a side-by-side or eccentric core-sheath type.
[0055] In addition, the segment in the present invention refers to a portion that can be separated from the composite fiber by solvent treatment, heat treatment, pressure treatment, etc. on the fiber cross-section of the composite fiber. If any segments are formed by the same polymer and the difference in cross-sectional area is within 10%, they are regarded as the same segment group.
[0056] When the composite fiber of this embodiment is used for textiles, in order to stably form multifilaments mixed with ultrafine fibers without being affected by the weaving structure, it is necessary to have two types of segments A and B in the fiber cross section and segment B has a smaller cross-sectional area than segment A.
[0057] If there are two types of segments A and B in the fiber cross section of the composite fiber, by dividing the segments A and B from the composite fiber after the textile is made, the ultrafine fibers including the segments B having a smaller cross-sectional area than the segments A can be uniformly mixed in the multifilament. Therefore, in the textile using the composite fiber of the present embodiment, the area of the flat portion caused by friction, wear, etc. can be reduced, and the softness can be improved because the ultrafine fibers have low bending rigidity, and the rebound feeling can be maintained because the general fibers have high bending recovery.
[0058] In addition, from the viewpoint that the area of the flat portion generated by friction, wear, etc. can be reduced by the presence of the ultrafine fibers including the segment B, it is preferred that three or more segments B are arranged on the periphery of the segment A. By arranging the segment B on the periphery of the segment A, the multifilament obtained after the division becomes a structure in which the normal fibers including the segment A are surrounded by the ultrafine fibers including the segment B, and when abraded with other raw materials, the ultrafine fibers including the segment B are preferentially abraded, thereby making the area of the generated flat portion smaller. From the above viewpoint, the more the number of segments B arranged on the periphery of the segment A, the more preferred, more preferably 5 or more, and particularly preferably 7 or more. On the other hand, from the viewpoint of maintaining the rebound feeling obtained from the normal fibers including the segment A, the number of segments B arranged on the periphery of the segment A is preferably 50 or less, more preferably 35 or less, and particularly preferably 20 or less.
[0059] In the fiber cross section of the composite fiber of this embodiment, the cross-sectional area S of each segment B is preferably B 1μm 2 ≦S B <65μm 2 .
[0060] The cross-sectional area S passing through each segment B B Less than 65μm 2 In the multifilament obtained from the segment B of the composite fiber, by including the ultrafine fiber with a small cross-sectional area of the segment B, the polishing suppression effect of reducing the area of the flat portion caused by friction, wear, etc. and the flexibility improvement effect obtained by low bending rigidity can be obtained. From the above viewpoint, S B The smaller the value, the more prominent the polishing suppression effect and the softness improvement effect can be, so S is more preferred. B Less than 50μm 2 , and preferably S B Less than 40μm 2 .
[0061] On the other hand, if the cross-sectional area S of each segment B is B If it is too small, it may cause the color development of dyes to decrease or the durability to decrease, such as easy fuzzing when worn. Therefore, the cross-sectional area S of each segment B is B Preferably 1 μm 2 More preferably S B 3μm 2 Above, preferably S B 7μm 2 above.
[0062] In the fiber cross section of the composite fiber of this embodiment, the cross-sectional area S per segment A is preferably A 65μm 2 ≦S A <700μm2 .
[0063] The cross-sectional area S passing through each segment A A 65μm 2 As described above, in the multifilament obtained by dividing the composite fiber into segment A and segment B, by including the conventional fibers having a large cross-sectional area in segment A, the bending recovery for exhibiting a preferred rebound feeling in textile products for clothing can be maintained, while taking into account the softness or polishing suppression effect brought by the ultrafine fibers having a small cross-sectional area in segment B.
[0064] From the above point of view, S A The larger the value, the more the rebound feeling can be improved by high bending recovery, so S is more preferred. A 80μm 2 Above, preferably S A 95μm 2 On the other hand, if S A If the value is too large, the normal fibers including segment A are easily cut due to friction, wear, etc., and the area of the resulting flat portion becomes larger, which may hinder the polishing suppression effect brought by the ultrafine fibers including segment B. Therefore, S A Preferably less than 700 μm 2 , more preferably S A Less than 500μm 2 , and preferably S A Less than 350μm 2 .
[0065] In addition, the cross-sectional area of the segment described in the present invention is obtained by embedding the composite fiber with an embedding agent such as epoxy resin, and taking an image of the fiber cross section perpendicular to the fiber axis using a scanning electron microscope (SEM) at a magnification that allows the composite fiber to be observed. The image taken is analyzed using image analysis software to calculate the cross-sectional area of a segment existing on the fiber cross section of the composite fiber, and the value rounded off to the first decimal place is used as the cross-sectional area of the segment. In addition, when there are multiple segments of the same type, the simple numerical average of the cross-sectional areas obtained for all segments of the same type is obtained, and the value rounded off to the first decimal place is used.
[0066] When the composite fiber of this embodiment is used in textiles, in order to further suppress the polishing phenomenon by making the ultrafine fibers obtained from the composite fiber segment B curl and form fine gaps between the fibers, or to obtain a dry touch caused by forming fine and complex grooves on the surface of the textile, or to obtain high water-repellent performance when a water-repellent treatment is performed, in the cross-section of the fiber, segment B needs to be formed by two polymers compounded into a parallel type or an eccentric core-sheath type.
[0067] By forming two polymers of segment B, each with a different center of gravity, such as Figure 1 The parallel type or eccentric core-sheath type as shown in (a) of the present invention is heat-treated after the segment B is divided, so that the ultrafine fibers including the segment B are greatly bent toward the polymer side that becomes highly shrinkable, and by making them continuous, a coil-like curling form can be exhibited. Furthermore, by controlling the distance between the centers of gravity of the polymers, any curling form can be exhibited, thereby further suppressing the polishing phenomenon achieved by forming fine gaps between the fibers, and achieving a dry touch by forming fine and complex concave-convex surfaces on the textile surface, which is the purpose of the present invention.
[0068] In addition, by having fine and complex concavoconvexities on the surface of the textile, when the water-repellent treatment is performed, high water-repellent performance due to the reduced contact area with water can be exhibited. In addition, as a composite structure of segment B, either a parallel type or an eccentric core-sheath type can be used. If it is set to the parallel type, the distance between the centers of gravity of the polymers becomes the maximum, so the curling expression can be improved. If it is set to the eccentric core-sheath type, the wear resistance of the ultrafine fiber including segment B can be further improved by covering the high shrinkage polymer with poor wear resistance with the low shrinkage polymer with excellent wear resistance.
[0069] In the composite fiber of the present embodiment, the two polymers forming the segment B are not particularly limited as long as they are a combination that produces a shrinkage difference during heat treatment, and a combination of polymers with different viscosities or polymers with different melting points can be considered, but from the viewpoint of easy control of the appearance of curl, a combination of polymers with different melting points is preferred. By using a combination with different melting points, when heat treatment is applied, the polymer on the lower melting point side shrinks first, so that the shrinkage difference between the polymers can be easily manifested.
[0070] In the composite fiber of the present embodiment, the polymer forming segment A is preferably the polymer having the lowest melting point among the polymers forming segment A and segment B. If the above relationship is achieved, the normal fiber including segment A obtained by segmenting the composite fiber becomes highly shrunk, and a difference in fiber length is generated between the normal fiber including segment B, which increases the space between the fibers and further improves the suppression of the polishing phenomenon which is the purpose of the present invention.
[0071] Furthermore, by forming more complex irregularities on the textile surface, which are a mixture of fine irregularities caused by the curling of the ultrafine fibers including segment B and coarse irregularities caused by the normal fibers including segment A, the dry touch or the water-repellent performance when water-repellent processing is performed can be further emphasized.
[0072] In addition, when there are two types of polymers forming segment A, from the viewpoint that the fibers including segment A and segment B both have crimps and thus the textile exhibits tensile properties, it is preferred that Figure 1 (b) or Figure 2 The segment A shown in the figure is formed of two polymers compounded in a side-by-side type or eccentric core-sheath type, and one of the two polymers is the polymer having the lowest melting point among the polymers constituting the segment A and the segment B.
[0073] In the composite fiber of the present embodiment, when the segment B is formed by two polymers composited into a parallel type or an eccentric core-sheath type, and the two polymers are a combination of polymers with different melting points, the area ratio of the low melting point polymer to the high melting point polymer is preferably in the range of 70 / 30 to 30 / 70. If it is within the above range, the curly shape caused by the shrinkage difference can be fully manifested without being affected by the hardening of the hand caused by the clogging of the mesh when the polymer on the low melting point side shrinks highly during the heat treatment, and a coarser inter-fiber space can be obtained.
[0074] In the segment B existing in the fiber cross section of the composite fiber of the present embodiment, the cross-sectional shape thereof is not limited, but from the viewpoint of forming a fiber morphology having fine gaps between fibers by causing the ultrafine fibers including the segment B to curl after the segment B is divided, the cross-sectional shape of the segment B is preferably as follows: Figure 1 A flat shape as shown in (a).
[0075] Here, the term "flat shape" refers to a shape that is elongated in a plan view, and specifically, refers to a shape in which a "flatness" in a later-described section is 1.1 or more.
[0076] By making the cross-sectional shape of the segment B present on the fiber cross section of the composite fiber of the present embodiment flat, the length of the major axis becomes a bottleneck and generates steric hindrance, so that the void effect caused by the curling can be maximized, and the dry touch caused by the fine concave-convex on the surface of the textile or the water-repellent performance when the water-repellent processing is implemented can be further highlighted. From the above point of view, the longer the length of the major axis is relative to the length of the minor axis, the better, and the flatness is preferably 1.2 or more, more preferably 1.5 or more, and more preferably 2.0 or more. On the other hand, if the flatness becomes too large, the area of the flat part during wear will increase, so the flatness is preferably 6.0 or less, more preferably 5.0 or less, and more preferably 4.0 or less.
[0077] The flatness of the segment in this embodiment is obtained by the following method.
[0078] First, the composite fiber is embedded with an embedding agent such as epoxy resin, and the cross-section of the fiber perpendicular to the fiber axis is imaged using a scanning electron microscope (SEM) at a magnification that allows the composite fiber to be observed. The image is analyzed using image analysis software, such as Figure 1As shown in (a), the straight line connecting the two points (a1, a2) farthest from any point on the periphery of the segment is taken as the major axis, and the straight line connecting the intersection point (b1, b2) of the straight line passing through the midpoint of the major axis and orthogonal to the major axis and the periphery of the fiber is taken as the minor axis, and the value of the length of the major axis divided by the length of the minor axis is calculated, and the value rounded off to the second decimal place is taken as the flatness. In addition, when there are multiple segments of the same type, the simple numerical average of the flatness obtained for all segments of the same type is obtained, and the value rounded off to the second decimal place is adopted.
[0079] In the segment A existing in the fiber cross section of the composite fiber of the present embodiment, the cross-sectional shape thereof is not limited, but from the viewpoint of reducing the flat portion even when the fibers including the segment A are worn when the textile obtained by dividing the segment A from the composite fiber is worn, the cross-sectional shape of the segment A is preferably as follows: Figure 1 A multi-lobed section having three or more convex portions on the periphery as shown in (a). By having convex portions on the periphery, the contact area with other raw materials during wear can be reduced, and the area flattened due to wear can be reduced. From the above viewpoint, the number of convex portions is more preferably 5 or more, and more preferably 7 or more. On the other hand, if the number of convex portions is too large, the effect gradually decreases, so the number of convex portions is preferably 20 or less, more preferably 15 or less, and more preferably 10 or less.
[0080] In the composite fiber of this embodiment, the purpose is to divide the segment A and segment B of the composite fiber after forming a textile so that the ultrafine fibers including the segment B are uniformly mixed in the multifilament. Therefore, the cross-sectional shape of the composite fiber is preferably as follows: Figure 1 The sea-island composite fiber having segments A and B as island components as shown in (a), or Figure 1 As shown in (c), the core-sheath composite fiber has segment A as the core and segment B as the sheath. Figure 1 The sea-island composite fiber shown in (a) can be divided into segment A and segment B by removing the sea component z. Figure 1 The core-sheath composite fiber as shown in (c) is formed by using non-miscible polymers with different bonds in the main chain to form the polymer constituting segment A and the polymer constituting segment B, respectively. The interface between segment A and segment B can be peeled and split by heat treatment or physical impact.
[0081] In addition, from the perspective of being able to stably divide segments A and B regardless of the polymers that form segments A and B, it is more preferred to use a sea island composite fiber in which segments A and B are island components, and the sea component is formed by a polymer that has the fastest dissolution rate relative to the solvent among the polymers that constitute the sea island composite fiber.
[0082] As for the dissolution rate of the polymer forming the sea component, if the simplification of the dissolution treatment in the high-order processing or the shortening of the time is taken into consideration, the dissolution rate ratio (sea component / island component) is preferably 100 or more, and more preferably 1000 or more, based on the polymer with the fastest dissolution rate among the polymers forming the island component. If the dissolution rate ratio is 1000 or more, the dissolution treatment can be completed in a short time, so in addition to increasing the process speed, a higher quality fabric can be obtained without unnecessary deterioration of the polymer of the island component. From the above point of view, the larger the dissolution rate ratio, the more preferable it is, but in terms of the stability of the polymer forming the sea component, the actual upper limit is 10000 or less.
[0083] The polymer forming the sea component is preferably selected from polymers that can be melt-formed and are more soluble than other components, such as polyester and its copolymers, polylactic acid, polyamide, polystyrene and its copolymers, polyethylene, and polyvinyl alcohol.
[0084] In addition, from the viewpoint of simplifying the elution process of the sea component, the polymer forming the sea component is preferably a copolyester, polylactic acid, polyvinyl alcohol, etc. that is easily soluble in an aqueous solvent or hot water, etc. In particular, since it is easily soluble in an aqueous solvent such as an alkaline aqueous solution while maintaining crystallinity, it is easy to process high-order processes such as not causing fusion between composite fibers even in false twisting processing with friction under heating, etc., and preferably a polyester copolymerized with 5 mol% to 15 mol% of 5-sodiosulfoisophthalic acid and a polyester copolymerized with 5 mass% to 15 mass% of polyethylene glycol having a weight average molecular weight of 500 to 3000 in addition to the 5-sodiosulfoisophthalic acid.
[0085] The composite fiber of the present embodiment is divided into segment A and segment B after a high-order process such as weaving is temporarily performed, and then heat-treated to obtain a multifilament in which normal fibers including segment A and crimped ultrafine fibers including segment B are uniformly mixed. In the multifilament, due to its special fiber morphology, a clothing textile having a dry touch or a soft hand with a sense of resilience that is not available in conventional raw materials can be obtained, and the degradation of the surface quality caused by friction and wear with other raw materials can be suppressed, and high water-repellent performance can be exhibited when a water-repellent process is performed.
[0086] In the multifilament of this embodiment, the area of the flat portion caused by friction, wear, etc. can be reduced, and in order to show a soft feel with a rebound feeling, it is necessary to have a multifilament containing two types of filaments A and filaments B, and there is one or more filaments B between any two filaments A in the multifilament, and the filaments B have a smaller fiber diameter than the filaments A.
[0087] In the present invention, any two filaments in a multifilament yarn are considered to be the same filaments if they are made of the same polymer and have a fiber diameter difference of within 10%.
[0088] In addition, the term "there are one or more filaments B between any two filaments A in the multifilament yarn" as used in the present invention means that the filaments A and the filaments B are uniformly mixed. Specifically, in the textile comprising the multifilament yarn of the present embodiment, an image is taken using a scanning electron microscope (SEM) at a magnification that allows observation of 15 or more filaments including two or more filaments A, and the image is analyzed using image analysis software such as Figure 4 As shown, circumscribed circles R1 and R2 are drawn in any two filaments A, and there is one or more filaments B in the range surrounded by the two common circumscribed lines (J1 and J2) of the two drawn circumscribed circles and the two circumscribed circles (R1 and R2). Figure 4 In the figure, it can be said that there are four filaments B within the range surrounded by the two common circumscribed lines (J1 and J2) and the two circumscribed circles (R1 and R2), and there is one or more filaments B between any two filaments A in the multifilament.
[0089] By having a filament B having a smaller fiber diameter than the longer filament A between any two filaments A in the multifilament yarn, the multifilament yarn becomes a fiber form in which the filaments A as normal fibers and the filaments B as ultrafine fibers are uniformly mixed. The area of the flat portion caused by friction, wear, etc. can be reduced, and the softness can be improved because the filaments B as ultrafine fibers have low bending rigidity, and the rebound feeling can be maintained because the filaments A as normal fibers have high bending recovery.
[0090] In the multifilament of this embodiment, the fiber diameter D of the filament B is preferably B 1μm≦D B <9μm.
[0091] The fiber diameter D of the filament B B Ultrafine fibers smaller than 9 μm can achieve the effect of reducing the area of flat portions caused by friction, wear, etc., and the effect of improving flexibility due to low bending rigidity. B The smaller the value, the more prominent the polishing suppression effect and the softness improvement effect can be, so D is more preferred. B Less than 8 μm, preferably D B Less than 7μm.
[0092] On the other hand, if the fiber diameter D of the filament B is BIf the diameter D of the filament B is too small, the color development property may be reduced when dyed with a dye or the durability may be reduced, such as fuzzing when worn. Therefore, the fiber diameter D of the filament B is preferably B Preferably 1 μm or more, more preferably D B 2 μm or more, and preferably D B 3μm or more.
[0093] In the multifilament of this embodiment, the fiber diameter D of the filament A is preferably A 9μm≦D A <30μm.
[0094] Fiber diameter D through filament A A When the thickness is 9 μm or more, the bending recovery for exhibiting a preferred spring back feeling in textile products for clothing can be maintained while achieving the softness and polish suppression effect of the ultrafine fibers having a small cross-sectional area including the segment B.
[0095] From the above point of view, D A The larger the value, the more the rebound feeling can be improved by high bending recovery, so D is more preferred. A 10 μm or more, and preferably D A On the other hand, if D A If the diameter is too large, the filament A, which is a normal fiber, is easily cut due to friction, wear, etc., and the area of the resulting flat portion becomes larger, which sometimes hinders the polishing suppression effect brought by the filament B, which is an ultrafine fiber. Therefore, D A Preferably less than 30 μm, more preferably D A Less than 25 μm, preferably D A Less than 20μm.
[0096] In the multifilament of the present embodiment, in order to further suppress the polishing phenomenon by making the filaments B, which are ultrafine fibers, show curls and form fine gaps between the fibers, or to obtain a dry touch caused by forming fine and complex irregularities on the surface of the textile, and to obtain high water-repellent performance when a water-repellent treatment is performed, in the cross section of the fiber, the filaments B need to be formed of two polymers compounded into a parallel type or an eccentric core-sheath type.
[0097] By forming the two polymers of the filament B, each with a different center of gravity, Figure 5If heat treatment is applied to the parallel type or eccentric core-sheath type as shown in (b), the filament B is greatly bent toward the polymer side that has become highly shrunk, and by making it continuous, a coil-like curling form can be exhibited. Furthermore, by controlling the distance between the centers of gravity of the polymers, any curling form can be exhibited, thereby further suppressing the polishing phenomenon achieved by forming fine gaps between the fibers, or achieving a dry touch caused by forming fine and complex concave-convex on the surface of the textile, which is the purpose of the present invention, can be achieved.
[0098] In addition, by having fine and complex irregularities on the surface of the textile, when water-repellent processing is applied, high water-repellent performance can be exhibited due to a reduced contact area with water.
[0099] In addition, the composite structure of the filament B may be either a parallel type or an eccentric core-sheath type. If the parallel type is used, the distance between the centers of gravity of the polymers becomes the largest, thereby improving the curling. If the eccentric core-sheath type is used, the wear resistance of the ultrafine fiber containing the filament B can be further improved by covering the high shrinkage polymer with poor wear resistance with a low shrinkage polymer with excellent wear resistance.
[0100] In the multifilament of the present embodiment, the two polymers forming the filaments B are not particularly limited as long as they are a combination that produces a shrinkage difference during heat treatment, but from the viewpoint of easily controlling the appearance of crimp, it is preferably a combination of polymers with different melting points. By using a combination with different melting points, when heat treatment is performed, the polymer on the lower melting point side shrinks first, so the shrinkage difference between the polymers can be easily manifested.
[0101] In the multifilament of the present embodiment, the polymer forming the filament A is preferably the polymer with the lowest melting point among the polymers forming the filament A and the filament B. If it is set in the above range, the filament A as a normal fiber becomes highly shrunk, and a difference in filament length is generated between the filament A and the filament B as an ultrafine fiber, which can increase the space between the fibers, and not only can the suppression of the polishing phenomenon as the purpose of the present invention be further improved, but also more complex concave-convex mixed with fine concave-convex caused by the curling of the filament B as an ultrafine fiber and coarse concave-convex caused by the filament A as a normal fiber is formed on the surface of the textile, which can further highlight the dry touch or the water-repellent performance when the water-repellent processing is performed.
[0102] In addition, when the polymers forming the filament A are two kinds, from the viewpoint that the textile can exhibit tensile properties by having both the filament A and the filament B have crimp, it is preferred that the filament A is composed of a composite such as Figure 6 The filaments A and B are formed of two polymers of a parallel type or eccentric core-sheath type as shown in (a), and one of the two polymers is the polymer with the lowest melting point among the polymers constituting the filaments A and B.
[0103] In the multifilament of the present embodiment, when the filament B is formed by two polymers compounded into a parallel type or an eccentric core-sheath type, and the two polymers are a combination of polymers with different melting points, as the area ratio of the low melting point polymer to the high melting point polymer, the low melting point polymer / high melting point polymer is preferably in the range of 70 / 30 to 30 / 70. If it is within the above range, it will not be affected by the hardening of the feel caused by the clogging of the mesh when the polymer on the low melting point side shrinks highly during the heat treatment, and the curling morphology caused by the shrinkage difference can be fully manifested, and a coarser inter-fiber space can be obtained.
[0104] In the multifilament yarn of the present embodiment, the cross-sectional shape of the filament B is not limited, but from the viewpoint of forming a fiber form having fine gaps between fibers by causing the filament B, which is an ultrafine fiber, to curl after the filament B is divided, the cross-sectional shape of the filament B is preferably as follows: Figure 5 A flat shape as shown in (b).
[0105] Here, the term "flat shape" refers to a shape that is elongated in a plan view, and specifically refers to a shape in which a "flatness" of the filament described later is 1.1 or more.
[0106] In the multifilament of the present embodiment, by making the cross-sectional shape of the filament B flat, the volume increases in the long axis direction, so the void effect caused by the curling can be maximized, and the dry touch caused by the fine and complex concave-convex of the textile surface or the water-repellent performance when the water-repellent processing is implemented can be further highlighted. From the above point of view, the longer the length of the major axis is relative to the length of the minor axis, the better, and the flatness is preferably 1.2 or more, more preferably 1.5 or more, and more preferably 2.0 or more. On the other hand, if the flatness becomes too large, the area of the flat part during wear will increase, so the flatness is preferably 6.0 or less, more preferably 5.0 or less, and more preferably 4.0 or less.
[0107] The flatness of the segment in this embodiment is obtained by the following method.
[0108] First, the multifilaments extracted from the textile are embedded with an embedding agent such as epoxy resin, and the cross-section of the fiber perpendicular to the fiber axis is imaged using a scanning electron microscope (SEM) at a magnification that allows the multifilaments to be observed. The captured images are analyzed using image analysis software, such as Figure 5As shown in (b), the straight line connecting the two points (a1, a2) farthest from any point on the periphery of the filament is taken as the major axis, and the straight line connecting the intersection point (b1, b2) of the straight line passing through the midpoint of the major axis and orthogonal to the major axis and the periphery of the fiber is taken as the minor axis, and the value of the length of the major axis divided by the length of the minor axis is calculated, and the value rounded off to the second decimal place is taken as the flatness. In addition, when there are a plurality of filaments of the same type in the multifilament, the simple numerical average of the flatnesses obtained for all filaments of the same type is obtained, and the value rounded off to the second decimal place is adopted.
[0109] In the multifilament of the present embodiment, the cross-sectional shape of the filament A is not limited, but from the viewpoint of reducing the flat portion even when the filament A as a normal fiber is worn when the textile is worn, the cross-sectional shape of the filament A is preferably as follows: Figure 5 A multi-lobed section having three or more convex portions on the periphery as shown in (a). By having convex portions on the periphery, the contact area with other raw materials during wear can be reduced, and the area flattened due to wear can be reduced. From the above viewpoint, the number of convex portions is more preferably 5 or more, and more preferably 7 or more. On the other hand, if the number of convex portions is too large, the effect gradually decreases, so the number of convex portions is preferably 20 or less, more preferably 15 or less, and more preferably 10 or less.
[0110] As the polymer used in the present embodiment, in terms of excellent processability, a thermoplastic polymer is preferably used. As the thermoplastic polymer, for example, a polyester, polyethylene, polypropylene, polystyrene, polyamide, polycarbonate, polymethyl methacrylate, polyphenylene sulfide and other polymer groups and copolymers thereof are preferably used. In particular, from the viewpoint that a high interfacial affinity can be given and a fiber with no abnormality in the composite cross section can be obtained, the thermoplastic polymer used in the present embodiment is preferably all the polymer groups and copolymers thereof. Among these, from the viewpoint that good color development can be obtained when the composite fiber and multifilament of the present embodiment are made into textiles and when dyeing, the thermoplastic polymer used in the composite fiber and multifilament is more preferably a polyester or polyamide polymer group and copolymers thereof, wherein polyethylene terephthalate and copolymers thereof are also preferably used, because a moderate sense of resilience can be obtained from high bending recovery.
[0111] In addition, when paying attention to environmental issues, in this embodiment, from the perspective of reducing environmental load, it is also appropriate to use plant-derived biopolymers or recycled polymers. Therefore, as the polymer used in the present embodiment, a recycled polymer that has been recycled by any method of chemical recycling, material recycling, and thermal recycling can be used.
[0112] Even when using a biopolymer or a recycled polymer, as described above, from the perspective of obtaining good color development during dyeing, a polyester-based or polyamide-based polymer group and its copolymers are preferred, and among them, recycled polyethylene terephthalate and its copolymers can be more preferably used because a moderate sense of resilience can be obtained from high bending recovery.
[0113] In addition, the polymer may contain various additives such as inorganic compounds such as titanium oxide, silicon dioxide, and barium oxide, colorants such as carbon black, dyes and pigments, flame retardants, fluorescent whitening agents, antioxidants, and ultraviolet absorbers.
[0114] Among these, it is also preferred to contain titanium oxide in the polymer. By containing titanium oxide in the polymer, the titanium oxide in the fiber diffusely reflects light, thereby not only suppressing the uneven appearance (glare) caused by the increase or decrease of reflection caused by the incident angle of light, but also improving the appearance quality, and the titanium oxide inside the fiber can also obtain functionality such as anti-transmission or ultraviolet shielding. In order to fully obtain the above effect, the content of titanium oxide in the composite fiber is preferably 0.5% by mass or more, more preferably 1.0% by mass or more, and further preferably 3.0% by mass or more. In addition, if the diffuse reflection of the light of titanium oxide increases, it sometimes causes a decrease in color rendering, so the content of titanium oxide in the fiber is preferably 10.0% by mass or less.
[0115] The combination of polymers with different melting points in the present embodiment refers to a combination of polymers with a melting point difference of more than 10°C if it is from a group of thermoplastic polymers that can be melt-formed, such as polyester, polyethylene, polypropylene, polystyrene, polyamide, polycarbonate, polymethyl methacrylate, polyphenylene sulfide, and their copolymers. If it is from a polyester system with ester bonds, a polyamide system with amide bonds, etc. that exists in the same polymer group with the same bonds in the main chain, it refers to a combination of polymers with a melting point difference of more than 5°C.
[0116] In particular, from the viewpoint of suppressing peeling and imparting stability to high-order processing or imparting durability to textiles, the combination of polymers is more preferably selected from the same polymer group having the same bonds in the main chain, such as polyesters of ester bonds and polyamides of amide bonds.
[0117] As a combination of a low melting point polymer and a high melting point polymer in the same polymer group, for example, the following various combinations can be listed. As polyester series, copolymerized polyethylene terephthalate / polyethylene terephthalate, polypropylene terephthalate / polyethylene terephthalate, polybutylene terephthalate / polyethylene terephthalate, thermoplastic polyurethane / polyethylene terephthalate, polyester elastomer / polyethylene terephthalate, polyester elastomer / polybutylene terephthalate can be listed. As polyamide series, nylon 6 or 66 / nylon 610, nylon 6-nylon 66 copolymer / nylon 6 or 610, polyethylene glycol (PEG) copolymerized nylon 6 / nylon 6 or 610, thermoplastic polyurethane / nylon 6 or 610 can be listed. As polyolefin series, ethylene-propylene rubber finely dispersed polypropylene / polypropylene, propylene-α-olefin copolymer / polypropylene, etc. can be listed.
[0118] Among these, from the perspective of obtaining good color development by dyeing when the composite fiber and multifilament of the present embodiment are made into textiles, the polymers with different melting points are more preferably a combination of polyester or polyamide. Among them, as a polyester, if it is set to a combination of copolymerized polyethylene terephthalate / polyethylene terephthalate, since a moderate rebound feeling can also be obtained from high bending recovery, it can be listed as a particularly preferred combination.
[0119] In addition, examples of copolymer components in the copolymerized polyethylene terephthalate include succinic acid, adipic acid, azelaic acid, sebacic acid, 1,4-cyclohexanedicarboxylic acid, maleic acid, phthalic acid, isophthalic acid, 5-sodiumsulfoisophthalic acid, and the like. Among these, polyethylene terephthalate copolymerized with 5 mol% to 15 mol% of isophthalic acid is preferred from the viewpoint of maximizing the shrinkage difference with polyethylene terephthalate.
[0120] In the textile in which a part of the textile is constituted by the multifilament of the present embodiment, since the multifilament has a fiber morphology in which normal fibers and ultrafine fibers are uniformly mixed, the area of the flat portion caused by friction, wear, etc. can be reduced, and since the ultrafine fibers have low bending rigidity, the softness can be improved, and since the normal fibers have high bending recovery, the rebound feeling is maintained, resulting in a textile that has both resistance to friction and feel that conventional raw materials do not have.
[0121] In addition, since the ultrafine fibers have curls, fine gaps are formed between the fibers due to the steric hindrance caused by the curls, and the friction surface is not fixed but can move flexibly, so the tolerance to friction is further improved, and the abrasion resistance can be greatly improved. In addition, by arranging the ultrafine fibers with curls on the surface layer, fine and complex concave and convex surfaces are formed on the surface of the textile, a dry touch can be obtained, or high water-repellent performance can be obtained when water-repellent processing is performed.
[0122] Therefore, it can be suitably used for general clothing such as jackets, skirts, underwear, and underwear, sportswear, and clothing materials. In addition, its characteristics can be effectively utilized and it can be suitably used for a wide range of fiber products such as carpets, sofas and other interior decoration products, car seats and other vehicle interior decoration products, cosmetics, masks, health products and other daily uses. However, it is particularly preferred to use it for clothing purposes from the viewpoint of suppressing the polishing phenomenon caused by wear with other materials during wear, obtaining a soft and dry touch, and showing high water-repellent performance when a water-repellent treatment is applied.
[0123] The multifilament of the present embodiment can be used for various textile products such as nonwoven fabrics and knitted fabrics. However, from the viewpoint of suitability for the above-mentioned clothing applications, a knitted fabric in which the multifilament of the present embodiment is a part is preferable.
[0124] The organization of the knitted fabric of the present invention is not particularly limited. For example, as the organization of the fabric when it is a woven fabric, there can be listed plain weave, twill weave, satin weave, modified plain weave, modified twill weave, modified satin weave, pattern weave, pattern weave, single overlap weave, double organization, multiple organization, warp pile weave, weft pile weave, leno weave, etc. In addition, as the organization of the knitted fabric, there can be listed circular knitting, weft knitting, warp knitting (including tricot warp knitting and raschel warp knitting), pile knitting, plain knitting, turban knitting, rib knitting, interlock knitting (double-sided knitting), rubber knitting, purl needle, denbigh structure, cord structure, warp knitted satin structure, chain organization, insertion organization, etc. The fabric and the knitted fabric can be any organization, but it is preferable to adopt an organization that is easy to form unevenness such as twill weave compared to plain weave, because the multifilament of this embodiment is easy to shrink and it is easy to form fine and complex unevenness on the surface of the cloth. When mixed with other fibers, it is desirable that the multifilaments of the present embodiment appear more on the surface.
[0125] When the knitted fabric of the present invention is a woven fabric, the total cover factor (CF) of the warp and weft is preferably 1000 to 3500. When the CF is 1000 or more, a highly durable woven fabric can be obtained in which the gaps formed at the tissue points are reduced and pilling and abrasion are not easily caused. From this viewpoint, a CF of 1500 or more is more preferred.
[0126] On the other hand, if CF is 3500 or less, the fine and complex concavities and convexities caused by the multifilaments will not be lost due to excessive restraint force generated by the tissue points, and the polishing phenomenon caused by abrasion with other raw materials during wearing can be suppressed, or a soft and dry touch can be obtained, and high water-repellent performance can be exhibited when water-repellent processing is performed. From this point of view, CF is more preferably 2800 or less.
[0127] The total cover factor (CF) mentioned here refers to the warp density and weft density of the fabric measured in the interval of 2.54 cm according to JIS L 1096:2010 8.6.1 and calculated as the warp yarn density [roots / 2.54 cm] × (total warp yarn fineness [dtex]) 1 / 2 + weft yarn density [root / 2.54cm] × (total weft yarn fineness [dtex]) 1 / 2 The value obtained by the formula of .
[0128] In the woven fabric of the present embodiment, in order to exhibit high water-repellent performance, it is preferred that the woven fabric includes a multifilament including two types of filaments A and filaments B, one or more filaments B exist between any two filaments A in the multifilament, the filaments B have a smaller fiber diameter than the filaments A, and are formed by two polymers compounded into a parallel type or an eccentric core-sheath type, and are subjected to water-repellent processing.
[0129] In addition, the so-called "there is one or more filaments B between any two filaments A" in the present invention means that the filaments A and the filaments B are uniformly mixed. Specifically, in the woven fabric of the present embodiment, for a cross-section perpendicular to the length direction and perpendicular to the fiber axis of the multifilament, an image is taken using a scanning electron microscope (SEM) at a magnification that allows observation of more than 15 filaments including two or more filaments A, and for the taken image, image analysis software such as Figure 4 As shown, circumscribed circles R1 and R2 are drawn in any two filaments A, and there is one or more filaments B in the range surrounded by the two common circumscribed lines (J1 and J2) of the two drawn circumscribed circles and the two circumscribed circles (R1 and R2). Figure 4 In the figure, it can be said that there are four filaments B within the range surrounded by the two common circumscribed lines (J1 and J2) and the two circumscribed circles (R1 and R2), and there is one or more filaments B between any two filaments A.
[0130] By having a filament B having a smaller fiber diameter than the filament A between any two filaments A in the multifilament yarn, the filament A as a normal fiber and the filament B as an ultrafine fiber are uniformly mixed in the multifilament yarn, and the two polymers forming the filament B are compounded into a fiber having different centers of gravity. Figure 5 If heat treatment is applied to the parallel type or eccentric core-sheath type as shown in (b), the filament B is greatly bent toward the polymer side that becomes highly shrinkable, and by making it continuous, a coil-like curling morphology can be exhibited. Thus, by mixing the curled ultrafine fibers with the ordinary fibers and arranging them on the surface layer, fine and complex concavoconvexities are formed on the surface of the textile, and when a water-repellent treatment is applied, the contact area with water becomes small, and high water-repellent performance can be exhibited.
[0131] In addition, the so-called knitted fabric with water repellent processing in the present invention is that the knitted fabric has water repellent performance in essence, and the water droplet sliding angle on the surface of the knitted fabric can be exemplified as less than 90 degrees. In the case where the knitted fabric of the present invention includes polyolefin, it has sufficient water repellent performance even if a water repellent agent is not given, so it is also a knitted fabric with water repellent processing. However, in the case of polyester or polyamide suitably used as clothing, sufficient water repellent performance cannot be directly obtained, so it is preferably to give a water repellent agent on the surface of the knitted fabric. Water repellent processing is performed in a manner that at least one side of the knitted fabric has water repellent performance. It is appropriate to select whether to perform water repellent processing only on a single side that needs water repellency, or to perform water repellent processing in a manner that both sides have water repellent performance as needed.
[0132] When a water repellent is applied to a knitted fabric and a water repellent treatment is performed, a fluorine-based or non-fluorine-based (for example, silicone-based, hydrocarbon-based, or other arbitrary water repellent) agent can be used as the water repellent agent. The type of water repellent agent is not particularly limited, and a fluorine-based water repellent agent of a fluorine-based compound containing a perfluoroalkyl group in which two or more hydrogen atoms of an alkyl group are replaced by fluorine atoms, or a non-fluorine-based water repellent agent containing no fluorine element can be used. From the perspective of environmental considerations, it is preferred to use a C6 fluorine-based water repellent agent or a non-fluorine-based water repellent agent having a perfluoroalkyl group with a carbon number of 6 or less. From the perspective of recyclability, it is more preferred to use a non-fluorine-based water repellent agent and the knitted fabric is substantially free of fluorine element.
[0133] In addition, the term "substantially free of fluorine element" as used herein means that the fluorine content in combustion ion chromatography is below the detection limit, i.e., below 25 ng / g. In addition, as non-fluorine-based water repellents, hydrocarbon-based water repellents such as silicone-based water repellents mainly composed of silicone compounds and paraffin-based water repellents mainly composed of paraffin-based compounds can be cited.
[0134] In order to obtain a woven fabric having the advantages of the present invention, that is, a soft and dry touch and high water-repellent performance, the amount of water-repellent attached is preferably 0.1% to 1% by mass. If the amount of water-repellent attached increases, the fibers are fixed to each other by the water-repellent, thereby not only hardening the hand feel, but also filling the unevenness between the water-repellent and the tactile feel becomes flat. On the other hand, if the amount of water-repellent attached is small, the water-repellent performance cannot be fully manifested. From these viewpoints, the amount of water-repellent attached is more preferably 0.2% to 0.8% by mass, and particularly preferably 0.3% to 0.5% by mass.
[0135] In the woven fabric of the present invention that has been at least water-repellent, fine and complex projections and depressions are formed on the surface of the textile by mixing curled ultrafine fibers with ordinary fibers and arranging them on the surface layer. As a result, when water droplets are added to the surface of the woven fabric, excellent water-repellent performance such as a lotus leaf effect can be exhibited. As the water-repellent performance, the water droplet sliding angle indicating the water droplet removal performance is preferably 1 degree to 20 degrees.
[0136] The water droplet sliding angle mentioned here is the angle at which the water droplets start to slide down when water droplets are slowly dripped on the surface of the woven fabric installed in a flat shape on a horizontal plate and the plate is slowly tilted at a constant speed. The smaller the water droplet sliding angle is, the better the water droplet removal performance is. The water droplet sliding angle refers to the tilt angle (°) when 20 μL of 20°C water is placed on the surface of the fabric using a solid-liquid interface analysis device ("DropMaster" 700 manufactured by Kyowa Interface Science Co., Ltd.), and the droplets slide down when the surface is slowly tilted from 0 degrees in units of 1 degree at a constant speed (target 1 degree / second).
[0137] If the water droplet sliding angle is 1 to 20 degrees, for example, when used for clothing, water droplets are not easily left on the knitted fabric when worn, and excellent water droplet removal performance without discomfort caused by wetness, etc. can be obtained. From the above viewpoint, the smaller the water droplet sliding angle is, the less water droplets are left on the knitted fabric when worn, and extremely high water droplet removal performance can be obtained. Therefore, the water droplet sliding angle is more preferably 1 to 15 degrees, and if it is set to 1 to 10 degrees, super water repellency that exceeds the lotus leaf in nature can be obtained, so it can be listed as a particularly preferred range.
[0138] When textiles with water-repellent function are used for clothing purposes, not only the initial water-repellent performance is required, but also practical durability with little decrease in water-repellent performance when repeatedly worn in daily scenes is required. From the above point of view, in the knitted fabric of the present invention that is at least subjected to water-repellent processing, it is preferred that the difference in the angle of water droplets falling before and after washing and drying are repeated 20 times is 0 to 20 degrees.
[0139] The difference in the water droplet falling angle before and after washing and drying are repeated 20 times mentioned here refers to the absolute value of the water droplet falling angle after washing 20 times using the JIS L1930-2014-C4M method and drying using the A method (hanging drying) for the woven fabric of the present invention that has been at least subjected to water-repellent processing, minus the absolute value of the water droplet falling angle before washing and drying.
[0140] If the difference in the water droplet sliding angle before and after washing and drying is repeated 20 times is 0 to 20 degrees, excellent water droplet removal without discomfort caused by wetness can be obtained for a long time, and it can be suitably used as casual wear. Furthermore, if it is 0 to 10 degrees, it can also be suitably used for sportswear or uniforms that require excellent durable water repellency assuming use in harsh environments, so it can be listed as a more preferred range.
[0141] An example of a method for producing the conjugate fiber and the multifilament yarn according to the present embodiment will be described in detail below.
[0142] In order to obtain the multifilament mixed with ultrafine fibers as the purpose of the present invention, various methods can be used, such as a method of separating ordinary fibers and ultrafine fibers from composite fibers, a method of mixing ordinary fibers and ultrafine fibers that are separately spun by an air nozzle, etc., and a spinning mixing method in which ordinary fibers and ultrafine fibers are ejected from the same spinning die and simultaneously wound. However, when used for textiles, in order to stably form multifilament mixed with ultrafine fibers without being affected by the structure such as weaving, it is preferred to use the following method, that is, a composite fiber having two types of segments A and B in the fiber cross section, and segment B having a smaller cross-sectional area than segment A, and a method of separating ordinary fibers and ultrafine fibers from the composite fiber.
[0143] In the composite fiber of this embodiment comprising two or more polymers, by setting the melt viscosity ratio of the polymers used to less than 5.0 and the difference in solubility parameter values to less than 2.0, a composite polymer flow can be stably formed and a fiber with a good composite cross-section can be obtained, which is preferred.
[0144] As a composite die used when producing the composite fiber of the present embodiment containing two or more polymers, for example, a composite die described in Japanese Patent Application Laid-Open No. 2011-208313 can be preferably used.
[0145] The present invention Fig.12 The composite die shown is assembled in a spinning pack in a state where three components, namely, a metering plate 1, a distribution plate 2, and a blowout plate 3, are stacked from top to bottom, and provided for spinning. Fig.12It is an example of using three polymers such as A polymer, B polymer and C polymer. In the existing composite die, it is difficult to composite more than 3 polymers, and it is still preferred to use Fig.12 The composite die using fine flow paths as shown above.
[0146] exist Fig.12 In the die mouth component illustrated, the metering plate 1 is responsible for measuring the amount of polymer in each ejection hole and each distribution hole and allowing the polymer to flow in, the distribution plate 2 is responsible for controlling the composite cross-section of the single fiber and its cross-sectional shape, and the ejection plate 3 is responsible for compressing and ejecting the composite polymer flow formed by the distribution plate 2.
[0147] In order to avoid the complexity of the description of the composite die, although not shown in the figure, for the components stacked above the metering plate 1, it is sufficient to use components that form a flow path in combination with a spinning machine and a spinning assembly. By designing the metering plate 1 in combination with the existing flow path components, the existing spinning assembly and its components can be directly and effectively utilized. Therefore, it is not necessary to specialize the spinning machine specifically for the die. In addition, multiple flow path plates can actually be stacked between the flow path-metering plate or between the metering plate 1-distribution plate 2. The purpose is to set a structure as follows, that is, a flow path for efficiently transferring the polymer is set in the cross-sectional direction of the die and the cross-sectional direction of the single fiber and introduced into the distribution plate 2.
[0148] In this way, the polymer flow with a cross section formed by the distribution plate 2 is contracted and ejected in the ejection plate 3. At this time, the ejection hole has the purpose of re-measuring the flow rate of the composite polymer flow, that is, the point of ejection amount and the draft on the spinning line (= pulling speed / extrusion line speed). The hole diameter and hole length are appropriately determined in consideration of the viscosity of the polymer and the ejection amount.
[0149] As a method for spinning the composite fiber and multifilament of the present embodiment, it can also be manufactured by melt spinning for the purpose of manufacturing long fibers, solution spinning methods such as wet and dry-wet spinning, melt blowing and spunbonding methods suitable for obtaining sheet-like fiber structures, etc., and from the perspective of improving productivity, melt spinning is preferred. In addition, in the melt spinning method, it can be manufactured by using a composite die described later, and the spinning temperature at this time is preferably set to a temperature at which the high melting point or high viscosity polymer mainly shows fluidity among the types of polymers used. The temperature showing fluidity varies depending on the molecular weight, but if it is set between the melting point of the polymer and the melting point + 60°C, it can be stably manufactured.
[0150] The composite fiber and multifilament of this embodiment can be stably produced if the discharge amount per single hole in the die is 0.1 g to 10 g / min / hole. At this time, the discharge amount is preferably determined according to the desired fiber diameter in consideration of winding conditions or stretching ratio, etc.
[0151] After the polymer flow from the ejection hole is cooled and solidified, it is given an oil agent and pulled by a roller with a predetermined circumferential speed. Here, the pulling speed is determined according to the ejection amount and the target fiber diameter. In the present invention, from the perspective of stably manufacturing composite fibers and multifilaments, the pulling speed of the roller in spinning can be set to about 500m / min to 6000m / min, which can be changed according to the physical properties of the polymer or the purpose of use of the fiber. In particular, from the perspective of forming a high orientation and improving mechanical properties, by setting it to 500m / min to 4000m / min and then stretching, not only can the uniaxial orientation of the fiber be promoted, but also the curling can be controlled by the heat shrinkage difference caused by the stress difference during stretching and the orientation difference during stretching between the composite polymers, so it is preferred.
[0152] During stretching, for example, in a stretching machine including one or more rollers, generally speaking, if the fiber contains a thermoplastic polymer that can be melt-spun, the fiber is smoothly stretched in the axial direction of the fiber by setting the circumferential speed ratio of the first roller at the preheating temperature to the second roller corresponding to the crystallization temperature, and is heat-set and wound by the second roller. Here, as the preheating temperature, it is preferred to appropriately set the preheating temperature based on the softening temperature such as the glass transition temperature of the polymer. As the upper limit of the preheating temperature, it is preferred to set it to a temperature at which the fiber path is not disturbed due to the spontaneous elongation of the fiber during the preheating process. For example, in the case of polyethylene terephthalate (PET) having a glass transition temperature of about 70°C, the preheating temperature is usually set to about 80°C to 95°C. In addition, in the case of a polymer that does not show glass transition, it is sufficient to perform a dynamic viscoelasticity measurement (tanδ) of the composite fiber and select a temperature above the peak temperature on the high temperature side of the obtained tanδ as the preheating temperature.
[0153] In addition, the stretching may be performed after the spun composite fiber and multifilament are temporarily wound, or may be performed immediately after spinning without temporarily winding, but it is more preferable to perform yarn processing accompanied by stretching. By performing yarn processing, the unevenness of the textile surface becomes more complex, and the resistance to friction, the feel, and the water-repellent function, which are the advantages of the present invention, can be improved.
[0154] Here, in the case of implementing yarn processing accompanied by drawing, it is preferred to use highly oriented undrawn yarns obtained by high-speed spinning. Highly oriented undrawn yarns have a structure with oriented amorphous and moderate crystal nuclei, and have a fast crystallization rate. They can prevent yarn breakage or pilling caused by a decrease in drawing tension by preventing welding in the heater, and are therefore suitable for yarn processing. There are some differences in the method for manufacturing such highly oriented undrawn yarns depending on the fiber diameter, polymer type, and viscosity, but in the research of the inventors and others, by selecting the winding speed during spinning from the range of 2000m / min to 4000m / min, a composite fiber with good yarn processing properties can be obtained.
[0155] The yarn processing is not particularly limited as long as it is a common yarn processing technique such as false twisting or uneven stretching, but from the perspective of changing the curling form to an uneven form and making the obtained touch or feel complex, it is more preferable to implement false twisting or uneven stretching.
[0156] The method of performing the false twisting process is not particularly limited as long as it is a general method, but in consideration of productivity, it is preferably performed using a friction false twisting machine using a disk or a belt. By performing the false twisting process, a multiple crimping form is formed by combining the crimping caused by the shrinkage difference with the mechanical crimping given by the false twisting process, and the concavoconvexity of the textile surface becomes more complex, which can improve the resistance to friction, the feel, and the water-repellent function that are the advantages of the present invention.
[0157] In order to stably produce the crimped yarn used in the present invention by false twisting, it is desirable to control the crimp form by the actual number of twists of the yarn bundle in the twisting region.
[0158] That is, the false twist number T (in times / m), which is the number of twists of the yarn bundle in the twisting area, can be determined based on the total fineness Df (in dtex) of the yarn bundle after the false twisting process. It is preferred to set the false twisting conditions such as the rotation speed or processing speed of the twisting mechanism in a manner that satisfies the following conditions.
[0159] 20000 / Df 0.5 ≦T≦40000 / Df 0.5
[0160] Here, the false twist number T is measured by the following method. That is, the yarn bundle traveling in the twisting area of the false twisting process is collected in a length of 50 cm or more to prevent the twist from being released just before the twisting. Then, the collected yarn sample is installed in a twist inspection machine, and the twist number obtained by measuring the twist number by the method described in JIS L1013 (2010) 8.13 is the false twist number T. When the false twist number satisfies the above conditions, a multiple curling form is formed by combining the curling caused by the shrinkage difference and the mechanical curling given by the false twisting process.
[0161] In addition, under the false twisting conditions, the stretching ratio in the twisting zone can be adjusted. The stretching ratio mentioned here is the stretching ratio calculated in the form of Vd / V0 using the circumferential speed V0 of the roller supplying the yarn to the twisting zone and the circumferential speed Vd of the roller provided immediately after the twisting mechanism. When the supply yarn is a drawn yarn, Vd / V0 can be set to 0.9 to 1.4 times. When the supply yarn is a highly oriented undrawn yarn, Vd / V0 can also be set to 1.2 to 2.0 times, and stretching can be performed simultaneously with the false twisting process. By setting the stretching ratio to the above range, the composite fiber in the multifilament can be given a curl as a whole without generating excessive tension in the twisting zone or relaxation of the yarn bundle.
[0162] Furthermore, from the viewpoint of firmly fixing the crimp obtained in the false twisting process, the false twisting temperature is preferably determined in the range of Tg+50°C to Tg+150°C based on the Tg of the polymer on the high Tg side of the composite polymer. The false twisting temperature referred to herein refers to the temperature of the heater provided in the twisting region. By setting the false twisting temperature in the above range, the structure of the polymer greatly twisted and deformed in the cross section of the composite fiber can be sufficiently fixed, so that the dimensional stability of the crimp obtained in the false twisting process can be improved.
[0163] In addition, it is also preferred to perform a stretching process by uneven stretching at a stretching ratio that does not exceed the range of the natural stretching ratio of the composite fiber, so as to obtain the thickness (thick and thin) of the stretched portion and the unstretched portion that appear randomly in the fiber axis. By performing uneven stretching, in addition to the difference in dyeability between the monofilaments, the difference in dyeability will also occur in the stretched portion and the unstretched portion, so the color depth is more emphasized, and the curling morphology in the stretched portion and the unstretched portion is also different, so when the cloth is made, the wood grain tone or feel like the natural raw material can be shown. In addition, if the false twisting process is continuously performed after the uneven stretching process, the raw material combining the wood grain tone and the feel caused by the multiple curling morphology can be obtained, so it can be listed as a more preferred range.
[0164] In addition, the composite fiber and multifilament of one embodiment of the present invention may be blended with other fibers before or after the yarn processing. The blending method is not particularly limited, and general blending methods such as interlaced blending and taslan blending can be used.
[0165] The composite fiber of the present embodiment is a sea-island composite fiber. When segment A and segment B are separated by removing the sea component, the sea component can be formed by a known polymer that can be dissolved in a solvent or hot water, and the composite fiber can be immersed in a solvent that can dissolve the polymer of the sea component and remove the polymer of the sea component. For example, when the polymer of the sea component is a copolymerized polyethylene terephthalate or polylactic acid formed by copolymerization of 5-sodium sulfoisophthalic acid or polyethylene glycol, an alkaline aqueous solution such as an aqueous sodium hydroxide solution can be used. As a method for treating the composite fiber of the present embodiment with an alkaline aqueous solution, for example, after making a woven fabric or a fiber structure containing the composite fiber, it is immersed in an alkaline aqueous solution. At this time, if the alkaline aqueous solution is heated to 50°C or above, the hydrolysis can be accelerated, so it is preferred. In addition, if a fluid dyeing machine is used, a large amount of treatment can be carried out at one time, so it is preferred from an industrial point of view.
[0166] When the multifilament of the present embodiment is used as a fiber product, after the composite fiber and multifilament of the present embodiment are made into textiles, water repellent, antistatic, flame retardant, hygroscopic, antibacterial, soft finishing, and other known post-processing can be used as needed. In a part of the fiber products, especially woven fabrics, which contain the multifilament of the present embodiment, the contact area with water becomes smaller when the water repellent processing is performed due to the presence of fine and complex concave-convex on the surface of the textile, thereby showing high water repellent performance, so it is particularly preferred to perform water repellent processing as a post-processing. In addition, the presence of fine and complex concave-convex on the surface of the textile can also improve the washing durability of these functional processing agents such as water repellent, antistatic, flame retardant, hygroscopic, antibacterial, and soft finishing.
[0167] When water repellent processing is performed, fluorine-based or non-fluorine-based (for example, silicone-based, hydrocarbon-based or other arbitrary water repellent) agents can be used as water repellent agents. The water repellent processing step is not particularly limited to filling method, spraying method, coating method, etc., but in terms of allowing the water repellent agent to penetrate into the inside of the woven fabric, the filling method is preferred.
[0168] In order to improve the durability of water repellency, it is preferred to use a crosslinking agent in the water repellent. As the crosslinking agent, at least one of melamine resin, blocked isocyanate compound (polymerization), glyoxal resin and imine resin can be used, and the crosslinking agent is not particularly limited.
[0169] The weaving and knitting method of the knitted fabric partially composed of the multifilament of the present embodiment is not particularly limited, and the knitting and knitting can be woven and knitted by a common method. When the knitted fabric is a fabric, for example, a water jet loom, an air jet loom, a rapier loom, a jacquard loom, etc. can be listed. In addition, when the knitted fabric is a knitted product, for example, a circular knitting machine, a warp knitting machine, etc. can be listed.
[0170] Example
[0171] The conjugate fiber and multifilament yarn of the present invention will be specifically described below with reference to Examples.
[0172] The following evaluations were performed on Examples and Comparative Examples.
[0173] A. Melt viscosity of polymer
[0174] The sheet-like polymer was set to a moisture content of 200 ppm or less by a vacuum dryer, and the melt viscosity was measured by a Capirograph manufactured by Toyo Seiki. In addition, as for the measurement temperature, the time from the sample being put into the heating furnace under a nitrogen environment to the start of the measurement was set to 5 minutes, and the shear rate was set to 1216s -1 The value of was evaluated as the melt viscosity of the polymer.
[0175] B. Melting point of polymer
[0176] The sheet-like polymer was set to a moisture content of less than 200 ppm by a vacuum dryer, weighed about 5 mg, and a differential scanning calorimeter (DSC) Q2000 manufactured by TA Instruments was used. After heating from 0°C to 300°C at a heating rate of 16°C / min, it was kept at 300°C for 5 minutes for DSC measurement. The melting point was calculated based on the melting peak observed during the heating process. A sample was measured 3 times, and the average value was taken as the melting point. In addition, when multiple melting peaks were observed, the top of the melting peak on the highest temperature side was taken as the melting point.
[0177] C. Fineness
[0178] The mass of 100 m of fiber was measured and the value was calculated by multiplying the value by 100. The above operation was repeated 10 times, and the average value was rounded off to the nearest decimal point and used as the fineness (dtex).
[0179] D. Flatness of segments in composite fibers
[0180] The composite fiber is embedded with an embedding agent such as epoxy resin, and the cross section of the fiber in the direction perpendicular to the fiber axis is imaged using a scanning electron microscope (SEM) manufactured by Hitachi at a magnification that allows one composite fiber to be observed. The image is analyzed using WinROOF manufactured by Mitani Shoji, a computer software, such as Figure 1As shown in (a), the straight line connecting the two points (a1, a2) farthest from any point on the periphery of the segment is taken as the major axis, and the straight line connecting the intersection point (b1, b2) of the fiber periphery and the straight line passing through the midpoint of the major axis and orthogonal to the major axis is taken as the minor axis, and the value of the length of the major axis divided by the length of the minor axis is calculated, and the value rounded off to the second decimal place is taken as the flatness. In addition, when there are multiple segments of the same type, the simple numerical average of the flatness obtained for all segments of the same type is obtained, and the value rounded off to the second decimal place is adopted.
[0181] E. The cross-sectional area of the segment in the composite fiber (S A , S B )
[0182] The composite fiber is embedded with an embedding agent such as epoxy resin, and the fiber cross section perpendicular to the fiber axis is imaged using a scanning electron microscope (SEM) manufactured by Hitachi at a magnification that allows observation of one composite fiber. The image is analyzed using WinROOF manufactured by Mitani Shoji, a computer software, to calculate the cross-sectional area (μm) of a segment in the fiber cross section of the composite fiber. 2 ), and the value rounded off to the first decimal place is taken as the cross-sectional area of the segment. In addition, when there are multiple segments of the same type, the cross-sectional area (μm) of all segments of the same type is calculated. 2 ) is a simple numerical average, with the value rounded to the first decimal place being used.
[0183] F. Flatness of filaments
[0184] The value is obtained by embedding a multifilament containing 10 or more filaments extracted from a textile with an embedding agent such as epoxy resin, and taking an image of the cross section of the fiber perpendicular to the fiber axis using a scanning electron microscope (SEM) manufactured by Hitachi at a magnification that allows the multifilament to be observed. The image is analyzed using WinROOF manufactured by Mitani Shoji, a computer software. Figure 5 As shown in (b), the straight line connecting the two points (a1, a2) farthest from any point on the periphery of the filament is taken as the major axis, and the straight line connecting the intersection point (b1, b2) of the straight line passing through the midpoint of the major axis and orthogonal to the major axis and the periphery of the fiber is taken as the minor axis, and the value of the length of the major axis divided by the length of the minor axis is calculated, and the value rounded off to the second decimal place is taken as the flatness. In addition, when there are a plurality of filaments of the same type in the multifilament, the simple numerical average of the flatness obtained for all filaments of the same type is obtained, and the value rounded off to the second decimal place is adopted.
[0185] G. Fiber diameter of filament (D A , D B)
[0186] The fiber diameter (μm) is obtained by embedding a multifilament containing more than 10 filaments extracted from a textile with an embedding agent such as epoxy resin, and taking an image of the fiber cross section perpendicular to the fiber axis using a scanning electron microscope (SEM) manufactured by Hitachi at a magnification that allows the multifilament to be observed. The image taken is analyzed using WinROOF manufactured by Mitani Shoji, a computer software, and the cross-sectional area of a filament present in the fiber cross section of the multifilament is measured. The diameter obtained by converting to a perfect circle is measured in μm units to the first decimal place, and the value rounded to the first decimal place is used as the fiber diameter (μm). In addition, when there are multiple segments of the same type, the simple numerical average of the fiber diameters obtained for all segments of the same type is obtained, and the value rounded to the first decimal place is used.
[0187] H. Fluorine content
[0188] The fluorine content was calculated by the following combustion ion chromatography measurement method.
[0189] (1) Preparation of samples: After the test base fabric was shredded, the freeze-pulverized sample was dried under reduced pressure (at room temperature for 2 hours).
[0190] (2) Adjustment of standard solution: Fluoride ion standard solution (1005 μg / mL, Wako Pure Chemical Industries, Ltd., Lot. KPP6061) was diluted with bromine internal standard solution to adjust the standard solution. Among these, the analytical data of the standard solution suitable for the concentration in the analysis sample was used to prepare the standard curve.
[0191] (3) Combustion ion chromatography of the sample: The sample was weighed and burned in a combustion tube of a combustion device ("AQF-100", manufactured by Mitsubishi Chemical Analytical Science Co., Ltd.) under the following conditions. The gas generated in the absorption unit ("GA-100", manufactured by Mitsubishi Chemical Analytical Science Co., Ltd.) was absorbed into the solution, and a portion of the absorption liquid was analyzed by an ion chromatograph ("ICS1500", manufactured by DIONEX). The sample was measured with n=2 according to the weighing, and the average value (ng / g) of the measured value was calculated. In addition, when the measured value was 25 ng / g or less, it was set as "below the detection limit".
[0192] <Combustion / Absorption Conditions>
[0193] Electric furnace temperature: Inlet 900℃, Outlet 1000℃
[0194] Gas: Ar / O2 200mL / min, O2 400mL / min
[0195] Absorption liquid: H2O 290μg / mL, internal standard Br 2μg / mL
[0196] Absorption volume: 10mL
[0197] <Ion chromatography / anion analysis conditions>
[0198] Mobile phase: 2.7mmol / L Na2CO3 / 0.3mmol / L NaHCO3
[0199] Flow rate: 1.50mL / min
[0200] Detector: Conductivity detector
[0201] Injection volume: 100μL
[0202] I. Evaluation of textile feel (softness, resilience, dryness)
[0203] The number of conjugate fibers was adjusted so that the cover factor in the warp direction (CFA) was 800 and the cover factor in the weft direction (CFB) was 1200, thereby producing a 2 / 1 twill fabric.
[0204] The CFA and CFB mentioned here are measured in accordance with JIS L 1096:2010 8.6.1 on the warp density and weft density of the fabric within a 2.54 cm interval, and are calculated according to CFA = warp yarn density [roots / 2.54 cm] × (total warp yarn fineness [dtex]) 1 / 2 , CFB = weft yarn density [root / 2.54cm] × (total weft yarn fineness [dtex]) 1 / 2 The obtained fabric was subjected to scouring, alkali treatment, wet heat treatment, heat setting, dyeing and water repellent treatment in sequence, and the three hand feelings of softness, rebound feeling and dry feeling were evaluated using the following method.
[0205] I-1. Softness
[0206] The evaluation was performed using a pure bending tester (KES-FB2) manufactured by Kato Tech using the following method. That is, a 20 cm × 20 cm fabric was held with an effective sample length of 20 cm × 1 cm, and the maximum curvature in the weft direction was ±2.5 cm. -1 The curvature is calculated to be 0.5 cm. -1 With 1.5cm -1 The difference in bending moment per unit width (gf cm / cm) divided by the difference in curvature 1cm -1 The value and curvature obtained are -0.5cm -1 -1.5cm -1The difference in bending moment per unit width (gf cm / cm) divided by the difference in curvature 1cm -1 The above action is performed three times at each position, and the simple numerical average of the results of the above action at a total of ten positions is obtained. The value is rounded to the fourth decimal place and multiplied by 100 to obtain the bending hardness B×10 -2 (gf cm 2 / cm). In addition, 1gf·cm 2 / cm=9.8mN·cm 2 / cm. According to the bending hardness B×10 -2 (gf cm 2 / cm), and the softness was evaluated into four grades based on the following criteria.
[0207] S: Excellent flexibility (bending hardness B×10 -2 ≦0.5)
[0208] A: Good flexibility (0.5 < bending hardness B × 10 -2 ≦1.0)
[0209] B: Soft (1.0 < bending hardness B × 10 -2 ≦1.5)
[0210] C: Poor flexibility (1.5 < bending hardness B × 10 -2 ).
[0211] I-2. Rebound
[0212] Using a pure bending tester (KES-FB2) manufactured by Kato Tech, a 20cm×20cm fabric was held with an effective sample length of 20cm×1cm, and the curvature when bent in the weft direction was calculated to be ±1.0cm -1 The above action was performed three times at each location, and the simple numerical average of the results of the above action at a total of ten locations was calculated. The value was rounded to the fourth decimal place and multiplied by 100 to obtain the bending recovery 2HB×10 -2 (gf·cm / cm). In addition, 1gf·cm / cm=9.8mN·cm / cm. According to the obtained bending recovery 2HB×10 -2 (gf·cm / cm), and the rebound feeling was evaluated in four levels based on the following criteria.
[0213] S: Excellent rebound feeling (bending recovery 2HB×10 -2 ≦0.5)
[0214] A: Good rebound feeling (0.5<bending recovery 2HB×10-2 ≦1.0)
[0215] B: Rebound (1.0<bending recovery 2HB×10 -2 ≦1.5)
[0216] C: Poor rebound feeling (1.5<bending recovery 2HB×10 -2 ).
[0217] I-3. Dry feeling
[0218] Using an automated surface tester (KES-FB4) manufactured by Kato Tech, a load of 50 g was applied to a 1 cm × 1 cm terminal wound with piano wire within a range of 10 cm × 10 cm of a 20 cm × 20 cm fabric, and the terminal was slid at a speed of 1.0 mm / sec to obtain the variation of the average friction coefficient MMD. The above action was performed three times at each location, and the simple numerical average of the results of the above action performed at a total of ten locations was obtained. The value rounded to the fourth decimal place and multiplied by 100 was taken as the friction variation (×10 -2 ). Based on the obtained friction changes, the dry feeling was evaluated in four levels according to the following criteria.
[0219] S: Excellent dry feeling (2.0 ≤ friction change)
[0220] A: Good dry feeling (1.5≦friction change<2.0)
[0221] B: Dry feeling (1.0≦friction change<1.5)
[0222] C: Poor dry feeling (friction change <1.0).
[0223] J. Textile function evaluation (stretchability, water repellency)
[0224] The number of conjugate fibers was adjusted so that the cover factor in the warp direction (CFA) was 800 and the cover factor in the weft direction (CFB) was 1200, thereby producing a 2 / 1 twill fabric.
[0225] The CFA and CFB mentioned here are measured in accordance with JIS L 1096:2010 8.6.1 on the warp density and weft density of the fabric within a 2.54 cm interval, and are calculated according to CFA = warp yarn density [roots / 2.54 cm] × (total warp yarn fineness [dtex]) 1 / 2 , CFB = weft yarn density [root / 2.54cm] × (total weft yarn fineness [dtex]) 1 / 2The obtained fabric was subjected to scouring, alkali treatment, wet heat treatment, heat setting, dyeing and water repellency treatment in sequence, and then the water repellency and stretchability were evaluated using the following method.
[0226] J-1. Stretchability
[0227] The stretchability is tested according to the elongation method A (constant rate elongation method) described in Item 8.16.1 of JIS L1096:2010. In addition, when the load of 17.6N (1.8kg) of the sample tape method is adopted, the test conditions are set as sample width 5cm×length 20cm, clamping interval 10cm, and stretching speed 20cm / min. In addition, the initial load is in accordance with the method of JIS L1096:2010, using a weight equivalent to a sample width of 1m. The simple numerical average of the results of three tests in the transverse direction of the fabric is calculated, and the value after rounding off after the decimal point is taken as the elongation (%). According to the obtained elongation, the stretchability is judged in three levels based on the following criteria.
[0228] S: Excellent stretchability (30≦ elongation)
[0229] A: Good stretchability (20≦elongation<30)
[0230] B: With stretchability (10≦elongation<20)
[0231] C: Poor stretchability (elongation < 10).
[0232] J-2. Water repellency (water droplet sliding angle)
[0233] The water repellency is measured by using a solid-liquid interface analyzer ("DropMaster" 700 manufactured by Kyowa Interface Science Co., Ltd.) to determine the tilt angle (°) when 20 μL of 20°C water is placed on a 20 cm × 20 cm fabric surface on a horizontal table and the fabric is slowly tilted from 0 degrees in units of 1 degree at a constant speed (target 1 degree / second) to allow the droplets to slide down. The simple numerical average of the results of the above operation at any five locations on the fabric is calculated, and the value after rounding off below the decimal point is the water droplet sliding angle (°). Based on the obtained water droplet sliding angle, the water repellency is judged in three levels based on the following criteria.
[0234] S: Excellent water repellency (water drop angle ≤ 10)
[0235] A: Good water repellency (10<water droplet sliding angle ≦15)
[0236] B: Water repellent (15<water drop falling angle ≦20)
[0237] C: Poor water repellency (20 < water droplet sliding angle).
[0238] K. Evaluation of textile surface quality (polish resistance, abrasion resistance)
[0239] The number of conjugate fibers was adjusted so that the cover factor in the warp direction (CFA) was 800 and the cover factor in the weft direction (CFB) was 1200, thereby producing a 2 / 1 twill fabric.
[0240] Here, the CFA is based on the warp yarn density [roots / 2.54cm] × (total warp yarn fineness [dtex]). 1 / 2 , CFB = weft yarn density [root / 2.54cm] × (total weft yarn fineness [dtex]) 1 / 2 The obtained fabric was subjected to scouring, alkali treatment, wet heat treatment, heat setting, dyeing treatment, and water repellent treatment in sequence, and then the two surface qualities of polishing resistance and abrasion resistance were evaluated using the following method.
[0241] K-1. Wear resistance
[0242] Using a whitening tester, the fabric is mounted on a sample holder at the center of the upper part of the device and rubbed against the friction surface at the lower part of the device for a certain period of time. The fabric that has been polished in actual wear is used as a sample sample, and the number of times when it is rubbed until a polished gloss equivalent to that of the actual wear sample is generated is used as a predetermined number of times, and the sample after rubbing at this time is used as a 1st-level sample. In addition, the sample after rubbing when the sample sample is rubbed at half the predetermined number of times is used as a 3rd-level sample, and the sample before rubbing is used as a 5th-level sample. The evaluation sample is rubbed, and the gloss of the sample after rubbing is compared with the sample by visual inspection under a D65 light source, and a grade judgment from 1st to 5th level is implemented on a 1-level scale. In addition, the case where it is duller than 3rd level and glossier than 5th level is set as 4th level, and the case where it is duller than 1st level and glossier than 3rd level is set as 2nd level. According to the obtained grade judgment results, the polish resistance is judged in four levels based on the following criteria.
[0243] S: Excellent polish resistance (grade: 5)
[0244] A: Good polish resistance (level judgment: 4)
[0245] B: Has polish resistance (level judgment: 2, 3)
[0246] C: Poor polish resistance (grade determination: grade 1).
[0247] K-2. Wear resistance
[0248] Regarding wear resistance, an Appearance Retention Tester (manufactured by Daiei Kagaku Seiki Seisakusho Co., Ltd.) was used to wet the fabric cut into a circle with a diameter of 6 cm with distilled water and then mounted on a disc. Furthermore, the fabric cut into a circle with a diameter of 11 cm was fixed on a horizontal plate that was kept dry. The disc with the fabric wetted with distilled water was brought into horizontal contact with the fabric fixed on the horizontal plate, and the two pieces of fabric were rubbed by making a circle with a diameter of 38 mm at the center of the disc with a load of 420 g and a speed of 85 rpm for 10 minutes. After the friction was completed, the discoloration and fading degree of the fabric mounted on the disc was graded from 1 to 5 using a gray scale for discoloration and fading with a 0.5-level scale. According to the obtained grade judgment results, the wear resistance was judged in four levels based on the following criteria.
[0249] S: Excellent wear resistance (grade judgment: 4.5 or above)
[0250] A: Good wear resistance (level judgment: 3.5, 4)
[0251] B: Good wear resistance (level judgment: 2.5, 3)
[0252] C: Poor abrasion resistance (grade determination: 2 or less).
[0253] [Example 1]
[0254] Prepare polyethylene terephthalate copolymerized with 8 mol % of 5-sodiumsulfoisophthalic acid and 9 mass % of polyethylene glycol (SSIA-PEG copolymerized PET, melt viscosity: 100 Pa·s, melting point: 233°C) as polymer 1, polyethylene terephthalate copolymerized with 7 mol % of isophthalic acid (isophthalic acid (Isophthalic Acid, IPA) copolymerized PET, melt viscosity: 140 Pa·s, melting point: 232°C) as polymer 2, and polyethylene terephthalate (PET, melt viscosity: 30 Pa·s, melting point: 254°C) as polymer 3.
[0255] After these polymers were melted at 290°C, polymer 1 / polymer 2 / polymer 3 were weighed in a mass ratio of 20 / 40 / 40 and flowed into a Fig.12 In the spinning assembly of the composite die shown in FIG. Figure 1 The sea-island composite fiber shown in (b) is Figure 1 In (b), in the form of a composite structure in which polymer 1 is arranged at z, polymer 2 is arranged at x1 and y1, and polymer 3 is arranged at x2 and y2, the polymer is ejected from the ejection hole.
[0256] The ejected composite polymer stream was cooled and solidified, and then provided with an oil agent, and then wound up at a spinning speed of 1500 m / min and stretched between rolls heated to 90° C. and 130° C. to produce composite fibers of 110 dtex-24 filaments.
[0257] Regarding the obtained composite fiber, in the cross section of the fiber, Figure 1 The outer periphery of the eight-leaf-shaped segment A of the parallel composite structure including x1 and x2 is arranged with 8 Figure 1 The flat segment B (flatness 3.0) of the parallel composite structure including y1 and y2 in (b). In addition, the cross-sectional area S of each segment A is A 167μm 2 , the cross-sectional area S of each segment B B 13μm 2 , segment B has a smaller cross-sectional area than segment A, and it can be confirmed that it is the composite fiber of the present invention.
[0258] The obtained composite fiber was used as warp and weft to obtain a 2 / 1 twill fabric. The obtained fabric was scoured in warm water at 80°C containing a surfactant for 10 minutes, and heated to 90°C using a 1% by mass sodium hydroxide aqueous solution in a jet dyeing machine to remove more than 99% of polymer 1, which is an easily soluble polymer. Subsequently, after a wet heat treatment was performed at 130°C for 30 minutes using a jet dyeing machine, heat setting was performed at 180°C for 1 minute under the condition of a draw ratio of 5%.
[0259] Next, for dyeing, the fabric was immersed in an aqueous solution containing a disperse dye (black) and a dyeing auxiliary as a dye, and dyed at a temperature of 130° C. for 60 minutes, and then washed. Subsequently, the fabric was immersed in an aqueous solution containing a reducing cleaning agent at a temperature of 80° C. for 20 minutes, and then washed and air-dried. Then, for water repellent processing, the film was immersed in a treatment liquid mixed with 4 mass% of "Neoseed" (registered trademark) NR-158 (manufactured by Nikka Chemical Co., Ltd., a non-fluorine-based (paraffin-based) water repellent, solid content 30%), 0.2 mass% of "BECKAMINE" (registered trademark) M-3 (manufactured by DIC Corporation), 0.15 mass% of catalyst ACX (manufactured by DIC Corporation), 1 mass% of isopropyl alcohol, and 94.65 mass% of water, and after squeezing out the film at a squeezing rate of 60% using a squeezing mill, it was dried using a pin tenter at 130°C for 2 minutes and cured at 170°C for 1 minute.
[0260] The obtained fabric contains uniformly mixed Figure 6(a) an eight-leaf filament A having a parallel composite structure including X1 and X2 and having Figure 6 (b) is a multifilament of a flat shape (flatness 3.0) of filament B having a parallel composite structure of Y1 and Y2. In addition, the fiber diameter of filament A is 15 μm, and the fiber diameter of filament B is 4 μm. Filament B has a smaller fiber diameter than filament A, and it can be confirmed that it is the multifilament of the present invention.
[0261] The fabric including the multifilament has a good rebound feeling (bending recovery 2HB: 0.8×10 -2 gf cm / cm(7.8×10 -2 mN·cm / cm)) and good flexibility (bending hardness B: 0.8×10 -2 gf cm 2 / cm(7.8×10 -2 mN cm 2 In addition, since the filament B, which is an ultrafine fiber, has a parallel composite structure and is curled, fine gaps are formed between the fibers due to the steric hindrance caused by the curling, and the friction surface is not fixed but can move flexibly, so the tolerance to friction becomes high, and it not only has good abrasion resistance (abrasion resistance: 4 levels) and wear resistance (discoloration and fading: 3.5 levels), but also because the curled ultrafine fibers are arranged on the surface layer, fine concave and convex are formed on the surface of the fabric, which also has a good dry feeling (friction change: 1.7×10 -2 ), is a fabric that combines the resistance to friction and the feel that existing raw materials do not have.
[0262] Furthermore, since the filament A also has a parallel composite structure, all the filaments in the multifilament have curls, and thus in addition to obtaining good stretchability (elongation: 25%), fine and complex concavities and convexities are formed, which are a mixture of fine concavities and convexities caused by the curling of the filament B which is an ultrafine fiber and coarse concavities and convexities caused by the filament A which is a normal fiber, and thus the fabric has a non-fluorine-based water-repellent agent with a fluorine content of less than the detection limit, i.e., less than 25 ng / g in the combustion ion chromatography measurement, and also obtains good water repellency (water droplet falling angle: 11°). The results are shown in the table.
[0263] [Examples 2 and 3]
[0264] In addition to making the cross-sectional area S of the composite fiber segment A A 66μm 2 , the cross-sectional area S of segment B B 5μm 2 (Example 2) The cross-sectional area S of segment A A 670μm2 , the cross-sectional area S of segment B B 50μm 2 Except for changing the discharge amount in the manner of (Example 3), all other operations were carried out in the same manner as in Example 1.
[0265] In Example 2, since the cross-sectional areas of the segments A and B of the composite fiber are reduced, the fiber diameters of the filaments A and B constituting the multifilaments of the obtained fabric are also reduced, thereby improving the softness and abrasion resistance of the fabric. In addition, as the fiber diameter decreases, the curled loops that appear become thinner, so the unevenness formed on the surface of the fabric becomes finer, and the water repellency is improved by reducing the contact area with water droplets.
[0266] In Example 3, since the cross-sectional areas of the segments A and B of the composite fiber are increased, the fiber diameters of the filaments A and B constituting the obtained multifilament fabric are also increased, and the resilience of the fabric is improved. In addition, as the fiber diameter increases, the curled loops that appear become coarser, so the unevenness formed on the fabric surface also becomes coarser, and the dry feeling is improved. The results are shown in the table.
[0267] [Example 4]
[0268] In addition to changing the cross-section shape to Figure 2 The entire process was carried out in the same manner as in Example 1, except that segment B was trilobate (flatness: 1.4) as shown in (a).
[0269] In Example 4, the filaments B in the obtained woven fabric were formed with irregularities, so that the diffuse reflection of light was increased and the uneven gloss (glare) of the woven fabric was suppressed. The results are shown in the table.
[0270] [Examples 5 and 6]
[0271] In addition to changing the cross-section shape to Figure 2 The segment A shown in (b) is four-leaf shaped (Example 5), Figure 2 Except for the circular shape shown in (c) (Example 6), all other steps are carried out in accordance with Example 1.
[0272] In Example 5, as the profile of the filament A in the obtained fabric increases, the spring back feeling increases. In addition, as the fiber diameter of the filament B increases, the curled loops that appear also become coarser, so the unevenness formed on the fabric surface also becomes coarser, and the dry feeling increases.
[0273] In Example 6, since the filaments A in the obtained fabric were round, not only the bending stiffness was reduced and the flexibility was improved, but also the distance between the centers of gravity of the polymers constituting the filaments A was lengthened, thereby improving the crimping performance and the stretchability. The results are shown in the table.
[0274] [Examples 7 and 8]
[0275] The entire process was carried out in accordance with Example 1, except that polymer 2 was changed to high-viscosity polyethylene terephthalate (high-viscosity PET, melt viscosity: 300 Pa·s, melting point: 254°C) (Example 7) and polypropylene terephthalate (PPT, melt viscosity: 130 Pa·s, melting point: 231°C) (Example 8).
[0276] In Example 7, since the multifilaments constituting the obtained woven fabric consist only of PET having no copolymer component, the woven fabric has an excellent springy feel.
[0277] In Example 8, combined with the rubber elasticity of PPT, the obtained fabric not only shows a softer feel, but also the curling of filaments A and B is improved, so that not only the stretching function is greatly improved, but also the concavoconvexity shown on the fiber surface becomes more complex, so the dry feeling or water repellency is also improved. The results are shown in the table.
[0278] [Example 9]
[0279] In addition to changing the cross-section shape to Figure 1 Except that segment B shown in (c) is an eccentric core-sheath type composite structure, all the operations were carried out in the same manner as in Example 8.
[0280] In Example 9, since the surface of the filament B in the obtained fabric was covered with PET, the wear of PPT was suppressed and good wear resistance was obtained. The results are shown in the table.
[0281] [Comparative Example 1]
[0282] Prepare polyethylene terephthalate copolymerized with 8 mol % of 5-sodiumsulfoisophthalic acid and 9 mass % of polyethylene glycol (SSIA-PEG copolymerized PET, melt viscosity: 100 Pa·s, melting point: 233°C) as polymer 1, polyethylene terephthalate copolymerized with 7 mol % of isophthalic acid (IPA copolymerized PET, melt viscosity: 140 Pa·s, melting point: 232°C) as polymer 2, and polyethylene terephthalate (PET, melt viscosity: 30 Pa·s, melting point: 254°C) as polymer 3.
[0283] After melting these polymers at 290°C, polymer 1 / polymer 2 / polymer 3 were weighed in a mass ratio of 30 / 35 / 35 and poured into a container having an assembled Fig.12 In the spinning assembly of the composite die shown in FIG. Figure 3 The sea-island composite fiber shown in (b) is Figure 3In the composite structure of (b), polymer 1 is arranged at z, polymer 2 is arranged at y1, and polymer 3 is arranged at y2, and the polymer is ejected from the ejection hole.
[0284] The ejected composite polymer stream was cooled and solidified, and then provided with an oil agent, and then wound up at a spinning speed of 1500 m / min and stretched between rolls heated to 90° C. and 130° C. to produce composite fibers of 110 dtex-24 filaments.
[0285] The obtained composite fiber has 12 layers with Figure 3 (b) A segment of a parallel composite structure including y1 and y2. In addition, the cross-sectional area of each segment is 20 μm 2 .
[0286] The obtained composite fiber was used as warp and weft to obtain a 2 / 1 twill fabric. The obtained fabric was subjected to scouring, alkali treatment, wet heat treatment, heat setting, dyeing and water repellent treatment in the same conditions as in Example 1 to obtain a fabric containing a filament having Fig.11 The parallel composite structure includes Y1 and Y2. In addition, the fiber diameter of the filament is 5 μm.
[0287] In Comparative Example 1, since only the ultrafine filaments were included, not only was the spring back feeling lacking, but also the fine irregularities formed on the surface of the fabric became flat, and the dry feeling was also impaired. The results are shown in the table.
[0288] [Comparative Example 2]
[0289] Polyethylene terephthalate copolymerized with 7 mol % of isophthalic acid (IPA copolymerized PET, melt viscosity: 140 Pa·s, melting point: 232° C.) was prepared as polymer 1, and polyethylene terephthalate (PET, melt viscosity: 30 Pa·s, melting point: 254° C.) was prepared as polymer 2.
[0290] After these polymers were melted at 290°C, polymer 1 / polymer 2 were weighed in a mass ratio of 50 / 50 and flowed into a spinning assembly equipped with a known composite die to form a spinning assembly as shown in FIG. Fig.11 The composite fiber shown, that is, Fig.11 In the form of a composite structure in which polymer 1 is arranged at X1 and polymer 2 is arranged at X2, the polymer is ejected from the ejection hole.
[0291] The ejected composite polymer stream was cooled and solidified, and then provided with an oil agent, and then wound up at a spinning speed of 1500 m / min and stretched between rolls heated to 90° C. and 130° C. to produce composite fibers of 110 dtex-48 filaments.
[0292] The obtained composite fiber was used as warp and weft to obtain a 2 / 1 twill fabric. The obtained fabric was subjected to scouring, alkali treatment, wet heat treatment, heat setting, dyeing and water repellent treatment in the same conditions as in Example 1 to obtain a fabric containing a filament having Fig.11 The parallel composite structure includes X1 and X2. In addition, the fiber diameter of the filament is 15 μm.
[0293] In Comparative Example 2, since only filaments, which are normal fibers, were included, not only the flexibility was lacking, but also the area of the flat portion generated by friction, abrasion, etc. of the fibers was large, so the abrasion resistance was also poor. The results are shown in the table.
[0294] [Comparative Example 3]
[0295] Polyethylene terephthalate copolymerized with 7 mol % of isophthalic acid (IPA copolymerized PET, melt viscosity: 140 Pa·s, melting point: 232° C.) was prepared as polymer 1, and polyethylene terephthalate (PET, melt viscosity: 30 Pa·s, melting point: 254° C.) was prepared as polymer 2.
[0296] After these polymers were melted at 290°C, polymer 1 / polymer 2 were weighed in a mass ratio of 50 / 50 and flowed into a spinning assembly equipped with a known composite die to form a spinning assembly as shown in FIG. Fig.11 The composite fiber shown, that is, Fig.11 In the form of a composite structure in which polymer 1 is arranged at X1 and polymer 2 is arranged at X2, the polymer is ejected from the ejection hole.
[0297] The ejected composite polymer stream was cooled and solidified, and then provided with an oil agent, and then wound up at a spinning speed of 1500 m / min and stretched between rolls heated to 90°C and 130°C to produce composite fibers of 55 dtex-24 filaments.
[0298] In addition, a composite fiber of 55 dtex-72 filaments was produced by the same method as described above except that the number of ejection holes of the composite die was changed.
[0299] The obtained two composite fibers were mixed using a known air nozzle to obtain a 2 / 1 twill fabric as warp and weft. The obtained fabric was subjected to scouring, alkali treatment, wet heat treatment, heat setting, dyeing, and water repellent treatment in the same conditions as in Example 1 to obtain a composite fiber mixed with Fig.11 The filament A of the parallel composite structure including X1 and X2 and having Fig.11A woven fabric of a multifilament of filament B having a parallel composite structure of Y1 and Y2. The fiber diameter of filament A is 15 μm, and the fiber diameter of filament B is 8 μm.
[0300] In Comparative Example 2, since the filaments A, which are normal fibers, and the filaments B, which are ultrafine fibers, are unevenly mixed, the area of the flat portion due to friction, wear, etc. is large in the area where the filaments A are concentrated, and the abrasion resistance is poor. The results are shown in the table.
[0301] [Example 10]
[0302] Prepare polyethylene terephthalate copolymerized with 8 mol % of 5-sodiumsulfoisophthalic acid and 9 mass % of polyethylene glycol (SSIA-PEG copolymerized PET, melt viscosity: 100 Pa·s, melting point: 233°C) as polymer 1, polyethylene terephthalate copolymerized with 7 mol % of isophthalic acid (IPA copolymerized PET, melt viscosity: 140 Pa·s, melting point: 232°C) as polymer 2, and polyethylene terephthalate (PET, melt viscosity: 30 Pa·s, melting point: 254°C) as polymer 3.
[0303] After melting these polymers at 290°C, polymer 1 / polymer 2 / polymer 3 were weighed in a mass ratio of 20 / 15 / 65 and poured into a container having an assembled Fig.12 In the spinning assembly of the composite die shown in FIG. Figure 1 The sea-island composite fiber shown in (a) is Figure 1 In the composite structure of (a), polymer 1 is arranged at z, polymer 2 is arranged at y1, and polymer 3 is arranged at x1 and y2, and the polymer is ejected from the ejection hole.
[0304] The ejected composite polymer stream was cooled and solidified, and then provided with an oil agent, and then wound up at a spinning speed of 1500 m / min and stretched between rolls heated to 90° C. and 130° C. to produce composite fibers of 110 dtex-24 filaments.
[0305] Regarding the obtained composite fiber, in the fiber cross section, Figure 1 The outer periphery of the segment A of the eight-leaf shape including x1 of (a) is configured with 8 Figure 1 The flat segment B (flatness 3.0) of the parallel composite structure including y1 and y2 in (a). In addition, the cross-sectional area S of each segment A is A 167μm 2 , the cross-sectional area S of each segment B B 13μm 2 , segment B has a smaller cross-sectional area than segment A, and it can be confirmed that it is the composite fiber of the present invention.
[0306] The obtained composite fiber was used as warp and weft to obtain a 2 / 1 twill fabric. The obtained fabric was scoured in warm water at 80°C containing a surfactant for 10 minutes, and heated to 90°C using a 1% by mass sodium hydroxide aqueous solution in a jet dyeing machine to remove more than 99% of polymer 1, which is an easily soluble polymer. Subsequently, after a wet heat treatment was performed at 130°C for 30 minutes using a jet dyeing machine, heat setting was performed at 180°C for 1 minute under the condition of a draw ratio of 5%.
[0307] Next, for dyeing, the fabric was immersed in an aqueous solution containing a disperse dye (black) and a dyeing auxiliary as a dye, and dyed at a temperature of 130° C. for 60 minutes, and then washed. Subsequently, the fabric was immersed in an aqueous solution containing a reducing cleaning agent at a temperature of 80° C. for 20 minutes, and then washed and air-dried.
[0308] Then, for water repellent processing, the film was immersed in a treatment liquid mixed with 4 mass% of "Neoseed" (registered trademark) NR-158 (manufactured by Nikka Chemical Co., Ltd., a non-fluorine-based (paraffin-based) water repellent, solid content 30%), 0.2 mass% of "BECKAMINE" (registered trademark) M-3 (manufactured by DIC Corporation), 0.15 mass% of catalyst ACX (manufactured by DIC Corporation), 1 mass% of isopropyl alcohol, and 94.65 mass% of water, and after squeezing out the film at a squeezing rate of 60% using a squeezing mill, it was dried using a pin tenter at 130°C for 2 minutes and cured at 170°C for 1 minute.
[0309] The obtained fabric contains uniformly mixed Figure 5 (a) comprising an eight-leaf filament A of X1 and having Figure 5 (b) is a multifilament of a flat shape (flatness 3.0) of filament B having a parallel composite structure of Y1 and Y2. In addition, the fiber diameter of filament A is 15 μm, and the fiber diameter of filament B is 4 μm. Filament B has a smaller fiber diameter than filament A, and it can be confirmed that it is the multifilament of the present invention.
[0310] The fabric including the multifilament has a good rebound feeling (bending recovery 2HB: 0.6×10 -2 gf cm / cm(5.9×10 -2 mN·cm / cm)) and good flexibility (bending hardness B: 1.0×10 -2 gf cm 2 / cm(9.8×10 -2 mN cm2 In addition, since the filament B, which is an ultrafine fiber, has a parallel composite structure and is curled, fine gaps are formed between the fibers due to the steric hindrance caused by the curling, and the friction surface is not fixed but can move flexibly, so the tolerance to friction becomes high, and it not only has polishing resistance (polishing degree: 6%) and abrasion resistance (discoloration and fading: 4 levels), but also has a dry feeling (friction variation: 1.3×10 -2 ), is a fabric that combines the resistance to friction and the feel that existing raw materials do not have.
[0311] Furthermore, by mixing crimped ultrafine fibers with ordinary fibers and arranging them on the surface layer, fine and complex concavities and convexities are formed on the surface of the textile, thereby providing a fabric having a non-fluorine-based water-repellent agent with a fluorine content below the detection limit, i.e., 25 ng / g or less in combustion ion chromatography measurement, and also obtaining water repellency (water droplet roll-off angle: 18°). The results are shown in the table.
[0312] [Example 11]
[0313] Polymer 1 / polymer 2 / polymer 3 were weighed in a mass ratio of 20 / 65 / 15 and flowed into the assembly. Fig.12 In the spinning assembly of the composite die shown in FIG. Figure 1 The sea-island composite fiber shown in (a) is Figure 1 The same procedures as in Example 9 were followed except that the polymer 1 was disposed at z, the polymer 2 was disposed at x1 and y1, and the polymer 3 was disposed at y2 in the composite structure of (a), and the polymer was ejected from the ejection hole.
[0314] In Example 11, since the segment A of the composite fiber is formed only of IPA copolymerized PET with a low melting point, the filament A constituting the multifilament of the obtained fabric becomes highly shrunk during heat treatment, so there is a difference in the length of the filament A and the filament B, and the unevenness formed on the surface of the fabric becomes coarser, and a good dry feeling can be obtained. In addition, due to the difference in the length of the filament, the gaps between the fibers become larger, so the area of the flat part generated by friction, wear, etc. becomes smaller, and excellent abrasion resistance is obtained. The results are shown in the table.
[0315] [Example 12]
[0316] Prepare nylon 6 (N6, melt viscosity: 190 Pa·s, melting point: 223°C) as polymer 1, polyethylene terephthalate copolymerized with 7 mol% of isophthalic acid (IPA copolymer PET, melt viscosity: 140 Pa·s, melting point: 232°C) as polymer 2, and polyethylene terephthalate (PET, melt viscosity: 30 Pa·s, melting point: 254°C) as polymer 3.
[0317] After these polymers were melted at 290°C, polymer 1 / polymer 2 / polymer 3 were weighed in a mass ratio of 20 / 40 / 40 and flowed into a Fig.12 In the spinning assembly of the composite die shown in FIG. Figure 1 The core-sheath composite fiber shown in (c) is Figure 1 In (c), in the form of a composite structure in which polymer 1 is arranged at x1, polymer 2 is arranged at y1, and polymer 3 is arranged at y2, the polymer is ejected from the ejection hole.
[0318] The ejected composite polymer stream was cooled and solidified, and then provided with an oil agent, and then wound up at a spinning speed of 1500 m / min and stretched between rolls heated to 90° C. and 130° C. to produce composite fibers of 110 dtex-24 filaments.
[0319] Regarding the obtained composite fiber, in the fiber cross section, Figure 1 The outer periphery of the segment A of the eight-leaf shape including x1 in (c) is configured with 8 Figure 1 The flat segment B (flatness 3.0) of the parallel composite structure including y1 and y2 in (a). In addition, the cross-sectional area S of each segment A is A 209μm 2 , the cross-sectional area S of each segment B B 15μm 2 , segment B has a smaller cross-sectional area than segment A, and it can be confirmed that it is the composite fiber of the present invention.
[0320] The obtained composite fiber was used as warp and weft to obtain a 2 / 1 twill fabric. The obtained fabric was scoured in warm water at 80°C containing a surfactant for 10 minutes, then subjected to a wet heat treatment at 130°C for 30 minutes using a jet dyeing machine to separate the sections A and B, and then subjected to heat setting at 180°C for 1 minute under a tentering ratio of 5%.
[0321] Next, for dyeing, the fabric was immersed in an aqueous solution containing a disperse dye (black) and a dyeing auxiliary as a dye, and dyed at a temperature of 130° C. for 60 minutes, and then washed. Subsequently, the fabric was immersed in an aqueous solution containing a reducing cleaning agent at a temperature of 80° C. for 20 minutes, and then washed and air-dried.
[0322] Then, for water repellent treatment, the fabric was immersed in a treatment solution mixed with 4% by mass of "Neoseed" (registered trademark) NR-158 (manufactured by Nikka Chemical Co., Ltd., a non-fluorine (paraffin) water repellent, 30% solid content), 0.2% by mass of "BECKAMINE" (registered trademark) M-3 (manufactured by DIC Corporation), 0.15% by mass of catalyst ACX (manufactured by DIC Corporation), 1% by mass of isopropyl alcohol, and 94.65% by mass of water, and after squeezing the fabric with a squeezing mill at a squeezing rate of 60%, it was dried at 130°C for 2 minutes with a pin tenter, and cured at 170°C for 1 minute. The obtained fabric contains a uniform mixture of Figure 5 (a) an eight-leaf filament A comprising X1 and having Figure 5 (b) is a multifilament of a flat shape (flatness 3.0) of filament B having a parallel composite structure of Y1 and Y2. In addition, the fiber diameter of filament A is 16 μm, and the fiber diameter of filament B is 4 μm. Filament B has a smaller fiber diameter than filament A, and it can be confirmed that it is the multifilament of the present invention.
[0323] Regarding the fabric including the multifilament, since the filament A is formed of nylon 6 with low elasticity and low melting point, in addition to having excellent softness, the filament A becomes highly shrunk during heat treatment, so there is a difference in the length of the filament A and the filament B, and the unevenness formed on the surface of the fabric becomes coarse, and a good dry feeling can be obtained. In addition, due to the difference in the length of the filament, the gap between the fibers becomes larger, so the area of the flat part generated by friction, wear, etc. becomes smaller, and excellent abrasion resistance is obtained. The results are shown in the table.
[0324] [Example 13]
[0325] The same procedures as in Example 1 were followed except that the conjugate fiber of 110 dtex-24 filaments obtained in Example 1 was false-twisted at a ratio of 1.05 to obtain false-twisted yarn of 105 dtex-24 filaments.
[0326] In Example 13, since the crimp development was improved by false twisting, not only the tensile function was greatly improved, but also the irregularities developed on the fiber surface became more complex, so the touch and water repellency were also improved. The results are shown in the table.
[0327] [Example 14]
[0328] Prepare polyethylene terephthalate copolymerized with 8 mol% of 5-sodiumsulfoisophthalic acid and 9 mass% of polyethylene glycol (SSIA-PEG copolymer PET, melt viscosity: 100 Pa·s, melting point: 233°C) as polymer 1, nylon 66 (N66, melt viscosity: 200 Pa·s, melting point: 255°C) as polymer 2, and nylon 610 (N610, melt viscosity: 80 Pa·s, melting point: 225°C) as polymer 3.
[0329] After melting these polymers at 280°C, polymer 1 / polymer 2 / polymer 3 were weighed in a mass ratio of 20 / 40 / 40 and poured into a pre-assembled Fig.12 In the spinning assembly of the composite die shown in FIG. Figure 1 The sea-island composite fiber shown in (b) is Figure 1 In (b), in the form of a composite structure in which polymer 1 is arranged at z, polymer 2 is arranged at x1 and y1, and polymer 3 is arranged at x2 and y2, the polymer is ejected from the ejection hole.
[0330] The ejected composite polymer stream was cooled and solidified, and then provided with an oil agent, and then wound up at a spinning speed of 1500 m / min and stretched between rolls heated to 40°C and 130°C to produce composite fibers of 90 dtex-24 filaments.
[0331] The obtained fabric contains uniformly mixed Figure 6 (a) an eight-leaf filament A having a parallel composite structure including X1 and X2 and having Figure 6 (b) is a multifilament of a flat shape (flatness 3.0) of filament B having a parallel composite structure of Y1 and Y2. In addition, the fiber diameter of filament A is 15 μm, and the fiber diameter of filament B is 4 μm. Filament B has a smaller fiber diameter than filament A, and it can be confirmed that it is the multifilament of the present invention.
[0332] The obtained composite fiber was used as warp and weft to obtain a 2 / 1 twill fabric. The obtained fabric was scoured in warm water at 80°C containing a surfactant, and polymer 1, which is an easily soluble polymer, was removed by 99% or more in warm water containing an aqueous sodium hydroxide solution using a jet dyeing machine. Subsequently, a wet heat treatment was performed at 110°C using a jet dyeing machine, and heat setting was performed at 180°C.
[0333] Next, for dyeing, the fabric was immersed in an aqueous solution containing an acid dye (black) and a dyeing auxiliary as a dye, and dyed at a temperature of 100° C. for 60 minutes, and then washed. Subsequently, the fabric was immersed in an aqueous solution containing a color fixing agent at a temperature of 80° C. for 20 minutes for color fixing, and then washed and air-dried.
[0334] Then, for water repellent processing, the fabric was immersed in an aqueous solution containing 4% by mass of "Neoseed" (registered trademark) NR-158 (manufactured by Nichika Chemical Co., Ltd., a non-fluorine-based water repellent), a crosslinking agent, and a penetrant, and after squeezing out the liquid at a squeezing rate of 60% using a squeezing mill, it was dried at 130°C using a pin tenter and cured at 170°C.
[0335] The obtained fabric contains uniformly mixed Figure 5 (a) an eight-leaf filament A comprising X1 and having Figure 5 (b) is a multifilament of a flat shape (flatness 3.0) of filament B having a parallel composite structure of Y1 and Y2. In addition, the fiber diameter of filament A is 16 μm, and the fiber diameter of filament B is 4 μm. Filament B has a smaller fiber diameter than filament A, and it can be confirmed that it is the multifilament of the present invention.
[0336] The fabric including the multifilaments is formed of nylon having low elasticity, and therefore has excellent softness. In addition, nylon is not easily abraded when worn, and therefore has excellent polishing resistance or abrasion resistance. The results are shown in the table.
[0337] [Comparative Example 4]
[0338] Polyethylene terephthalate copolymerized with 8 mol % of 5-sodiumsulfoisophthalic acid and 9 mass % of polyethylene glycol (SSIA-PEG copolymerized PET, melt viscosity: 100 Pa·s, melting point: 233°C) was prepared as polymer 1, and polyethylene terephthalate (PET, melt viscosity: 30 Pa·s, melting point: 254°C) was prepared as polymer 2.
[0339] After these polymers were melted at 290°C, polymer 1 / polymer 2 were weighed in a mass ratio of 20 / 80 and flowed into a spinning assembly equipped with a known composite die to form a spinning assembly as shown in FIG. Figure 3 The composite fiber shown in (a) is Figure 3 In the composite structure of (a), polymer 1 is arranged at z and polymer 2 is arranged at x1 and y1, and the polymer is ejected from the ejection hole.
[0340] The ejected composite polymer stream was cooled and solidified, and then provided with an oil agent, and then wound up at a spinning speed of 1500 m / min and stretched between rolls heated to 90° C. and 130° C. to produce composite fibers of 110 dtex-48 filaments.
[0341] Regarding the obtained composite fiber, in the fiber cross section, Figure 3 The outer periphery of the segment A of the eight-leaf shape including x1 in (a) is configured with 8 Figure 3 The flat shape (flatness 3.0) of segment B including y1 in (a). In addition, the cross-sectional area S of each segment A is A 167μm 2 , the cross-sectional area S of each segment B B 13μm 2 The obtained composite fiber was used as warp and weft to obtain a 2 / 1 twill fabric. The obtained fabric was subjected to scouring, alkali treatment, wet heat treatment, heat setting, dyeing and water repellent treatment in the same conditions as in Example 1 to obtain a fabric containing uniformly mixed Fig.10 (a) an octaphallic filament A comprising X1 and Fig.10 (b) is a woven fabric of a multifilament of Y1 including filaments B having a flat shape (flatness 3.0). The fiber diameter of the filaments A is 15 μm, and the fiber diameter of the filaments B is 4 μm.
[0342] In Comparative Example 4, since the filament B, which is an ultrafine fiber, has no crimp, not only is there no unevenness on the fabric surface and the dry feeling is lacking, but also, since the friction surface is fixed during the friction and abrasion of the fibers, both the filament A and the filament B are abraded, and the area of the flat portion generated becomes larger, so the abrasion resistance is also poor. The results are shown in the table.
[0343] Industrial Applicability
[0344] The composite fiber, multifilament, and knitted fabric of the present invention have a special fiber morphology in which the cross-sectional configuration within the composite fiber and the fiber configuration in the multifilament are precisely controlled, so that a textile having a dry touch or a soft feel with a resilient feel can be obtained, and the degradation of the surface quality caused by friction and wear with other raw materials can be suppressed, and high water-repellent performance can be exhibited when a water-repellent treatment is performed.
[0345] Therefore, it can be suitably used for general clothing such as jackets, skirts, underwear, and underwear, sportswear, and clothing materials. In addition, its characteristics can be effectively utilized and it can be suitably used for a wide range of fiber products such as carpets, sofas and other interior decoration products, car seats and other vehicle interior decoration products, cosmetics, masks, health products and other daily uses. However, it is particularly preferred to use it for clothing purposes from the viewpoint of suppressing the polishing phenomenon caused by wear with other materials during wear, obtaining a soft and dry touch, and showing high water-repellent performance when a water-repellent treatment is applied.
[0346]
[0347]
[0348]
[0349]
[0350] Description of Figure Numbers
[0351] x1, x2: polymers forming segment A
[0352] y1, y2: polymers forming segment B
[0353] z: polymers that form the sea component
[0354] a1, a2: the two points farthest from each other
[0355] b1, b2: The intersection of the fiber periphery and the straight line that passes through the midpoint of the straight line connecting the two points farthest apart (a1 and a2) and intersects perpendicularly
[0356] R1, R2: circumscribed circle
[0357] J1, J2: shared external tangent
[0358] X1, X2: polymers forming filament A
[0359] Y1, Y2: polymers forming filament B
[0360] 1: Metering board
[0361] 2: Distribution board
[0362] 3: Ejection plate
Claims
1. A composite fiber having two types of segments A and B in the cross section of the fiber, wherein the segment B has a smaller cross-sectional area than the segment A and is formed by two polymers composited into a side-by-side type or an eccentric core-sheath type.
2. The composite fiber according to claim 1, wherein Three or more segments B are arranged on the periphery of segment A in the fiber cross section.
3. The composite fiber according to claim 1 or 2, wherein The cross-sectional area S of each segment B on the fiber cross section B 1μm 2 ≦S B <65μm 2 . The composite fiber according to claim 1 or 2, which is a sea-island composite fiber having segments A and B as island components, wherein the sea component is formed by a polymer having the fastest dissolution rate in a solvent among polymers constituting the sea-island composite fiber.
5. A multifilament obtained by dividing the composite fiber according to claim 1 or 2 into segments A and B.
6. A fiber product, at least a part of which comprises the multifilament according to claim 5.
7. A multifilament comprising two types of filaments, filament A and filament B, wherein there is one or more filaments B between any two filaments A in the multifilament, the filaments B having a smaller fiber diameter than the filaments A and being formed by two polymers compounded into a parallel type or an eccentric core-sheath type.
8. The multifilament according to claim 7, wherein Fiber diameter D of filament B B 1μm≦D B <9μm.
9. A woven fabric, at least a part of which comprises the multifilament according to claim 7 or 8.
10. The knitted fabric according to claim 9, which is subjected to water-repellent treatment.
11. A woven fabric comprising a multifilament comprising two kinds of filaments, filament A and filament B, wherein there is one or more filaments B between any two filaments A in the multifilament, the filaments B have a smaller fiber diameter than the filaments A and are formed by two polymers compounded into a parallel type or an eccentric core-sheath type, and the water droplet sliding angle of the woven fabric is 1 degree to 20 degrees, and the woven fabric is subjected to water-repellent processing.
12. The braided fabric according to claim 11, wherein: The difference in the water droplet falling angle before and after washing by the JIS L1930-2014-C4M method and drying by the A method (hanging drying) were repeated 20 times was 0 to 20 degrees.
13. The braided fabric according to claim 11 or 12, wherein: The fluorine content measured by combustion ion chromatography was 25 ng / g or less.
Citation Information
Patent Citations
Bulky composite false twist textured yarn and its production
JP2000314038A
Composite spinneret and method for producing conjugated fiber
JP2011208313A
Composite fiber
JP2017186680A